Secondary battery, preparation method thereof and electric device

By using lithium manganese iron phosphate particles in the positive electrode active material of lithium ion batteries, combining the first lithium iron phosphate particles and the second lithium iron phosphate particles, the particle size and component ratio are optimized, and the problem of poor storage performance of lithium manganese iron phosphate at high temperature is solved, and good storage and circulation performance at high temperature is achieved.

CN119852342AActive Publication Date: 2025-04-18CONTEMPORARY AMPEREX TECHNOLOGY CO LTD
View PDF 9 Cites 0 Cited by

Patent Information

Application Number
CN202410027059.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-01-08
Publication Date
2025-04-18
Estimated Expiration
2044-01-08

AI Technical Summary

Technical Problem

As the positive electrode active material of lithium ion batteries, lithium iron phosphate has poor storage performance at high temperatures.

Method used

By using lithium manganese iron phosphate particles in the positive electrode active material, combining the first lithium iron phosphate particles and the second lithium iron phosphate particles, the particle size and component ratio are optimized, and the manganese dissolution amount and electrochemical reaction path are controlled.

Benefits of technology

The secondary battery has achieved good storage and cycling performance under high temperature conditions, and the solid content and kinetic performance of the cathode slurry are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119852342A_ABST
    Figure CN119852342A_ABST
Patent Text Reader

Abstract

The invention provides a secondary battery, a preparation method thereof and an electric device. Particularly, the invention provides a secondary battery which comprises a positive pole piece, a negative pole piece, an isolating membrane and an electrolyte, the positive pole piece comprises a positive active material, the positive active material comprises lithium manganese iron phosphate particles, the primary average particle size of the lithium manganese iron phosphate particles is 120-600nm, and the manganese dissolution amount of the secondary battery is less than or equal to 50ppm.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of secondary batteries, and in particular to a secondary battery, a preparation method thereof, and an electrical device. Background Art

[0002] As a positive electrode active material for lithium-ion batteries, lithium manganese iron phosphate has a higher voltage platform, theoretical energy density, theoretical specific capacity and lower cost than lithium iron phosphate. However, lithium manganese iron phosphate has a poorer high temperature (60°C) storage performance than lithium iron phosphate.

[0003] Therefore, it is necessary to provide a positive electrode active material containing lithium manganese iron phosphate, which has good high temperature storage performance. Summary of the invention

[0004] The present application is made in view of the above-mentioned problems, and its purpose is to provide a secondary battery with good high-temperature storage performance, a preparation method thereof, and an electrical device.

[0005] The inventors have discovered that the above objectives can be achieved by adopting the technical solution of the present application.

[0006] The first aspect of the present application provides a secondary battery, comprising a positive electrode plate, a negative electrode plate, a separator and an electrolyte, wherein the positive electrode plate comprises a positive electrode active material, the positive electrode active material comprises lithium iron manganese phosphate salt particles, and the primary average particle size of the lithium iron manganese phosphate salt particles is 120-600nm, wherein the manganese dissolution amount of the secondary battery is ≤50ppm.

[0007] The secondary battery of the present application has good high-temperature storage performance. In addition, the secondary battery of the present application also has good high-temperature cycle performance and a higher positive electrode slurry solid content.

[0008] In any embodiment, the positive electrode active material further includes first lithium iron phosphate salt particles, and the primary average particle size s1 of the first lithium iron phosphate salt particles satisfies 500 nm≤s1≤3000 nm.

[0009] When the positive electrode active material also includes first lithium iron phosphate salt particles, and the primary average particle size s1 of the first lithium iron phosphate salt particles satisfies 500nm≤s1≤3000nm, the secondary battery of the present application has lower manganese dissolution, better high temperature storage performance, better high temperature cycle performance, and higher positive electrode slurry solid content.

[0010] In any embodiment, based on the total area of ​​the positive electrode active material in the cross section of the positive electrode sheet, the area of ​​the first lithium iron phosphate salt particles accounts for 2%-30%, and the area of ​​the lithium manganese iron phosphate salt particles accounts for 70%-98%.

[0011] In any embodiment, the positive electrode active material further includes second lithium iron phosphate salt particles, and the primary average particle size s2 of the second lithium iron phosphate salt particles satisfies 30 nm≤s2≤200 nm.

[0012] When the positive electrode active material also includes second lithium iron phosphate salt particles, and the primary average particle size s2 of the second lithium iron phosphate salt particles satisfies 30nm≤s2≤200nm, the secondary battery of the present application has lower manganese dissolution, better high temperature storage performance, and better high temperature cycle performance.

[0013] In any embodiment, based on the total area of ​​the positive electrode active material in the cross section of the positive electrode sheet, the area of ​​the second lithium iron phosphate salt particles accounts for 1-10%; the area of ​​the first lithium iron phosphate salt particles accounts for 2-25%; the area of ​​the lithium manganese iron phosphate salt particles accounts for 70%-97%.

[0014] In any embodiment, the lithium manganese iron phosphate particles have a molecular formula Li m Fe x Mn r P y O j Q q , wherein Q comprises at least one of Al, Na, K, Mg, Cu, Cr, Zn, Pb, Ca, Co, Ni, Sr, Nb, V, Ti, B, S, Si, N, F, Cl, Br, 0.95≤m≤1.15, x>0, r>0, 0.9≤x+r≤1, 0.95≤y≤1, 3.5≤j≤4, 0≤q≤0.1, and / or

[0015] The first lithium iron phosphate salt particle has a molecular formula Li m1 Fe x1 P y1 O j1 Q1 q1 , wherein Q1 includes at least one of Al, Na, K, Mg, Cu, Mn, Cr, Zn, Pb, Ca, Co, Ni, Sr, Nb, V, Ti, B, S, Si, N, F, Cl, Br, 0.95≤m1≤1.15, 0.9≤x1≤1, 0.95≤y1≤1, 3.5≤j1≤4, 0<q1≤0.1, and / or

[0016] The second lithium iron phosphate salt particle has a molecular formula Li m2 Fe x2 P y2 O j2 Q2 q2, wherein Q2 includes at least one of Al, Na, K, Mg, Cu, Mn, Cr, Zn, Pb, Ca, Co, Ni, Sr, Nb, V, Ti, B, S, Si, N, F, Cl, and Br, 0.95≤m2≤1.15, 0.9≤x2≤1, 0.95≤y2≤1, 3.5≤j2≤4, and 0≤q2≤0.1.

[0017] In any embodiment, in the first lithium iron phosphate salt particles, Q1 includes at least one of Ti, V, Mg, and Nb, and the content of Ti, V, Mg, and / or Nb is 1000-10000 ppm based on the total weight of the first lithium iron phosphate salt particles.

[0018] In any embodiment, the specific surface area (BET) of the first lithium iron phosphate salt particles is 3 m 2 / g-8m 2 / g.

[0019] When the specific surface area (BET) of the first lithium iron phosphate salt particles is 3 m 2 / g-8m 2 / g, the secondary battery of the present application has lower manganese dissolution, higher positive electrode slurry solid content, and higher positive electrode sheet compaction density.

[0020] In any embodiment, the carbon content of the first lithium iron phosphate salt particles is Cx1 weight %, calculated based on the total weight of the first lithium iron phosphate salt particles, wherein 0.8≤Cx1≤2.0.

[0021] In any embodiment, based on the total weight of the first lithium iron phosphate salt particles, the carbon content of the first lithium iron phosphate salt particles is Cx1 weight %, and the ratio z1 of the specific surface area of ​​the first lithium iron phosphate salt particles to Cx1 satisfies 1.5≤z1≤8.5.

[0022] In any embodiment, the primary average particle size of the lithium manganese iron phosphate salt particles is 150-210nm, the primary average particle size s1 of the first lithium iron phosphate salt particles satisfies 870nm≤s1≤3000nm, and / or the primary average particle size s2 of the second lithium iron phosphate salt particles satisfies 60nm≤s2≤200nm.

[0023] In any embodiment, the capacity ratio of the first lithium iron phosphate salt particles is η≥88%, where η is defined as:

[0024] A battery using the first lithium iron phosphate salt particles as the positive electrode active material is charged and discharged twice at a constant current rate of 0.1C in the voltage range of 2.0V to 3.75V, and then charged and discharged once at a constant current rate of 1C. In the charge and discharge test at a rate of 1C, the capacity value at a discharge voltage of 3.2V is extracted and recorded as C1, the capacity value extracted and discharged to 2.0V is C2, and η=C1 / C2, wherein the charging process includes constant voltage charging, a constant voltage of 3.75V, and a constant voltage cut-off current of 50μA.

[0025] In any embodiment, the first lithium iron phosphate salt particles satisfy at least one of (a)-(f):

[0026] (a) Dv10 of the first lithium iron phosphate salt particles is ≥ 0.2 μm;

[0027] (b) the Dv50 of the first lithium iron phosphate particles is 0.5-5 μm;

[0028] (c) Dv90 of the first lithium iron phosphate salt particles is ≤10 μm;

[0029] (d) Dv99 of the first lithium iron phosphate salt particles is ≤12 μm;

[0030] (e) The powder compaction density of the first lithium iron phosphate salt under a pressure of 3 tons is ≥ 2.25 g / cm 3 ;

[0031] (f) The powder resistivity of the first lithium iron phosphate salt is less than 60Ω·cm.

[0032] In any embodiment, the aspect ratio of the second lithium iron phosphate salt particles is ≥ 1.3.

[0033] When the aspect ratio of the second lithium iron phosphate salt particles is ≥1.3, the secondary battery of the present application has better high-temperature storage performance, lower manganese dissolution, better high-temperature cycle performance, and higher gram capacity.

[0034] In any embodiment, the ratio W of the diffraction peak intensity of the (020) crystal plane to the diffraction peak intensity of the (211) crystal plane of the second lithium iron phosphate salt particle is ≥1.03.

[0035] When the ratio W of the (020) crystal plane diffraction peak intensity to the (211) crystal plane diffraction peak intensity of the second lithium iron phosphate salt particle is ≥1.03, the secondary battery of the present application has better high-temperature storage performance, lower manganese dissolution, better high-temperature cycle performance, and higher gram capacity.

[0036] In any embodiment, the first lithium iron phosphate salt particles are mainly obtained by the following preparation method:

[0037] Providing a raw material containing at least a lithium source, an iron source, a phosphorus source, optionally a carbon film-forming agent, optionally a carbon source, and optionally a modifier, and performing at least two sintering steps, wherein:

[0038] The temperature of the first sintering is 500℃-760℃, and can be 550℃-720℃;

[0039] The temperature of the second sintering is 700°C-800°C, and can be optionally 720°C-780°C.

[0040] In any embodiment, the first lithium iron phosphate salt particles are mainly obtained by the following preparation method:

[0041] Providing raw materials containing at least a lithium source, an iron source, a phosphorus source, a carbon source, a carbon film-forming agent, and a modifier, and performing at least two sintering steps, wherein:

[0042] The carbon content of the material after the first sintering is 0.01 wt%-0.79 wt%, optionally 0.05 wt%-0.4 wt%;

[0043] The carbon content of the material after the second sintering is 0.8 wt % to 2.0 wt %, and can be optionally 1.0 wt % to 1.6 wt %.

[0044] In any embodiment, the preparation method of the first lithium iron phosphate salt particles comprises the following steps:

[0045] The first pulverization is performed after the first sintering, and the second pulverization is performed after the second sintering, wherein:

[0046] The Dv50 of the product after the first pulverization is 300nm-1200nm, and can be optionally 400nm-1100nm;

[0047] The Dv50 of the product after the second pulverization is 500nm-5000nm, and can be optionally 700nm-2500nm.

[0048] A second aspect of the present application provides an electric device, which includes the secondary battery according to the first aspect of the present application. BRIEF DESCRIPTION OF THE DRAWINGS

[0049] Figure 1 Schematic diagram of a secondary battery according to one embodiment of the present application.

[0050] Figure 2 yes Figure 1 An exploded view of a secondary battery according to an embodiment of the present application is shown.

[0051] Figure 3 is a schematic diagram of a battery module according to an embodiment of the present application.

[0052] Figure 4 It is a schematic diagram of a battery pack according to one embodiment of the present application.

[0053] Figure 5 yes Figure 4 An exploded view of a battery pack according to an embodiment of the present application is shown.

[0054] Figure 6 FIG. 1 is a schematic diagram of an electric device using a secondary battery according to an embodiment of the present application as a power source.

[0055] Figure 7 This is a scanning electron microscope image of the first lithium iron phosphate salt particles with the primary particle size marked according to one embodiment of the present application.

[0056] Description of reference numerals:

[0057] 1 battery pack; 2 upper box; 3 lower box; 4 battery module; 5 secondary battery; 51 shell; 52 electrode assembly; 53 top cover assembly DETAILED DESCRIPTION

[0058] Hereinafter, the secondary battery, its manufacturing method and the implementation mode of the electrical device of the present application are specifically disclosed in detail with appropriate reference to the accompanying drawings. However, there may be cases where unnecessary detailed descriptions are omitted. For example, there are cases where detailed descriptions of well-known matters and repeated descriptions of actually the same structure are omitted. This is to avoid the following description from becoming unnecessarily lengthy and to facilitate the understanding of those skilled in the art. In addition, the drawings and the following descriptions are provided for those skilled in the art to fully understand the present application and are not intended to limit the subject matter described in the claims.

[0059] "Scope" disclosed in the present application is limited in the form of lower limit and upper limit, and a given range is limited by selecting a lower limit and an upper limit, and the selected lower limit and upper limit define the boundary of a special range. The scope limited in this way can be including end values ​​or not including end values, and can be arbitrarily combined, that is, any lower limit can be combined with any upper limit to form a scope. For example, if the scope of 60-120 and 80-110 is listed for a specific parameter, it is understood that the scope of 60-110 and 80-120 is also expected. In addition, if the minimum range values ​​1 and 2 are listed, and if the maximum range values ​​3, 4 and 5 are listed, the following scope can be all expected: 1-3, 1-4, 1-5, 2-3, 2-4 and 2-5. In the present application, unless otherwise specified, the numerical range "ab" represents the abbreviation of any real number combination between a and b, wherein a and b are real numbers. For example, the numerical range "0-5" means that all real numbers between "0-5" are listed in this document, and "0-5" is just an abbreviation of these numerical combinations. In addition, when a parameter is expressed as an integer ≥ 2, it is equivalent to disclosing that the parameter is, for example, an integer of 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, etc.

[0060] Unless otherwise specified, all embodiments and optional embodiments of the present application can be combined with each other to form a new technical solution.

[0061] Unless otherwise specified, all technical features and optional technical features of this application can be combined with each other to form a new technical solution.

[0062] If there is no special explanation, all steps of the present application can be performed sequentially or randomly, preferably sequentially. For example, the method includes steps (a) and (b), which means that the method may include steps (a) and (b) performed sequentially, or may include steps (b) and (a) performed sequentially. For example, the method may further include step (c), which means that step (c) may be added to the method in any order. For example, the method may include steps (a), (b) and (c), or may include steps (a), (c) and (b), or may include steps (c), (a) and (b), etc.

[0063] If there is no special explanation, the "include" and "comprising" mentioned in this application are open-ended or closed-ended. For example, the "include" and "comprising" may mean that other components not listed may also be included or only the listed components may be included or only the listed components may be included.

[0064] If not specifically stated, in this application, the term "or" is inclusive. For example, the phrase "A or B" means "A, B, or both A and B". More specifically, any of the following conditions satisfies the condition "A or B": A is true (or exists) and B is false (or does not exist); A is false (or does not exist) and B is true (or exists); or both A and B are true (or exist).

[0065] As a positive electrode active material for lithium-ion batteries, lithium iron manganese phosphate has a higher voltage platform, theoretical energy density, theoretical specific capacity and lower cost than lithium iron phosphate. However, lithium iron manganese phosphate has a poorer high temperature (60°C) storage performance than lithium iron phosphate. Therefore, it is necessary to provide a positive electrode active material comprising lithium iron manganese phosphate, which has better high temperature storage performance.

[0066] Based on this, the present application proposes a technical solution to solve the above technical problems.

[0067] The first aspect of the present application provides a secondary battery, comprising a positive electrode plate, a negative electrode plate, a separator and an electrolyte, wherein the positive electrode plate comprises a positive electrode active material, the positive electrode active material comprises lithium iron manganese phosphate salt particles, and the primary average particle size of the lithium iron manganese phosphate salt particles is 120-600nm, wherein the manganese dissolution amount of the secondary battery is ≤50ppm.

[0068] The ionic conductivity and electronic conductivity of lithium manganese iron phosphate salt are poor, and are greatly affected by the particle size. When the material contains lithium manganese iron phosphate salt with a larger particle size, the solid phase transmission of lithium ions will be greatly restricted, and the electron transmission path during the electrochemical reaction is long, and the gram capacity and kinetic performance of the material will be significantly reduced. Studies have found that when the surface of the lithium manganese iron phosphate material is in a charged state, the surface oxidizability is strong, and due to the Jan-Taylor effect, the surface oxygen atoms are easy to react with the protons of the electrolyte, resulting in manganese dissolution and electrolyte loss. Therefore, the particle size of lithium manganese iron phosphate salt should not be designed to contain too many small particles, that is, the micropowder content needs to be controlled at a low level. Experiments have found that the surface activity of small particles with a particle size of less than 120nm will increase significantly. This application adopts lithium manganese iron phosphate salt with a low manganese dissolution amount, and optimizes the particle size at the same time, so that the secondary battery of this application has good high temperature storage performance, good high temperature cycle performance and high positive electrode slurry solid content, and has good kinetic performance and high gram capacity.

[0069] In some embodiments, the primary average particle size of the manganese iron phosphate lithium salt particles can be 140-500nm. In some embodiments, the primary average particle size of the manganese iron phosphate lithium salt particles can be 120nm, 130nm, 140nm, 150nm, 160nm, 170nm, 180nm, 190nm, 200nm, 210nm, 220nm, 230nm, 240nm, 250nm, 260nm, 270nm, 280nm, 290nm, 300nm, 350nm, 400nm, 450nm, 480nm, 490nm, 500nm, 550nm, 600nm, or a range consisting of any two of the above primary average particle sizes or a value in the range.

[0070] In some embodiments, the manganese dissolution amount of the secondary battery is ≤48ppm. In some embodiments, the manganese dissolution amount of the secondary battery is ≤45ppm. In some embodiments, the manganese dissolution amount of the secondary battery is ≤40ppm. In some embodiments, the manganese dissolution amount of the secondary battery is ≤35ppm. In some embodiments, the manganese dissolution amount of the secondary battery is ≤30ppm. In some embodiments, the manganese dissolution amount of the secondary battery is ≤28ppm. In some embodiments, the manganese dissolution amount of the secondary battery is ≤25ppm. In some embodiments, the manganese dissolution amount of the secondary battery is ≤24ppm. In some embodiments, the manganese dissolution amount of the secondary battery is ≤20ppm. In some embodiments, the manganese dissolution amount of the secondary battery is ≤18ppm. In some embodiments, the manganese dissolution amount of the secondary battery is ≤17ppm. In some embodiments, the manganese dissolution amount of the secondary battery is ≤16ppm. In some embodiments, the manganese dissolution amount of the secondary battery is ≤15ppm. In some embodiments, the manganese dissolution amount of the secondary battery is ≤14ppm. In some embodiments, the manganese dissolution amount of the secondary battery is ≤ 12 ppm.

[0071] In the present application, the term "primary average particle size" refers to the average value of the primary particle sizes of all particles, wherein the primary particle size refers to the longest distance connecting two points on the edge in a cross-sectional view.

[0072] The primary average particle size of the lithium iron manganese phosphate salt particles can be measured by methods and equipment known in the art. For example, it can be tested by scanning electron microscopy and long diameter statistical method. As an example, an argon ion beam is used to cut the pole piece perpendicular to the large surface of the positive pole piece to expose the cross section, and the cross section is photographed by a scanning electron microscope. The boundary between the first positive electrode active layer and the second positive electrode active layer of the cross section is clear. The particle size of the positive electrode active layer containing the lithium iron manganese phosphate salt particles is statistically analyzed by the long diameter statistical method. Specifically, the total number of lithium iron manganese phosphate salt particles with a primary particle size greater than 10nm and the primary particle size and of the lithium iron manganese phosphate salt particles with a primary particle size greater than 10nm can be counted in the electron microscope scanning photo. The primary average particle size of the lithium iron manganese phosphate salt particles = the primary particle size of the total lithium iron manganese phosphate salt particles / the total number of lithium iron manganese phosphate salt particles. In the primary particle size statistical process, particles with a primary particle size of 0 < ≤ 10nm are not within the statistical range.

[0073] The amount of manganese dissolved can be measured by methods and equipment known in the art. For example, the ICP test process can be referred to: retrieve the fully charged cell after 100 cycles, disassemble it in the glove box, take out the anode electrode in the drying room, and use a ceramic knife to gently scrape 1g of material from the center of the electrode to ensure that the entire active material layer is scraped off to avoid different manganese content at different thicknesses. Seal it with a ziplock bag and send it to the laboratory. Prepare an electronic scale, heating plate, 150ml quartz beaker, watch glass, funnel, 100ml volumetric flask, pliers (heat-insulating gloves), weighing spoon, dust-free paper, etc.; confirm whether the electronic scale calibration date is within the validity period. It cannot be used after the validity period has expired and needs to be recalibrated; turn on the power, the heating plate can be heated to 250°C normally; weigh 0.2000±0.005g of powder in a beaker; acidification treatment: prepare a dilute sulfuric acid solution with a volume ratio of 1:4 (concentrated sulfuric acid: ultrapure water = 1:4); add 20ml of the prepared dilute sulfuric acid solution to the beaker; First, turn on the heating plate for preheating. After the temperature reaches 250℃, place the sample for digestion for 30 minutes. Place a quartz cover on the mouth of the beaker to reduce the volatilization of the acid. After the sample is digested for 30in, take it out and cool it to room temperature. Transfer the digested sample to a 100ml glass volumetric flask for volume adjustment. Then proceed according to the ICP standard test process: the test equipment temperature is 22+2℃, and the humidity is <60%; select the trace element method for the test method; run the calibration standard: use the configured standard solution to determine the standard curve; select the element as Mn; finally, the Mn dissolution amount can be obtained after testing.

[0074] In some embodiments, the positive electrode active material further includes first lithium iron phosphate salt particles, and the primary average particle size s1 of the first lithium iron phosphate salt particles satisfies 500 nm≤s1≤3000 nm.

[0075] In a specific embodiment, as shown in the attached Figure 7As shown in the scanning electron microscope image of the first lithium iron phosphate salt particle, the line segment marked by the double arrows in the particle is the primary particle size defined in this application.

[0076] In some embodiments, the first lithium iron phosphate salt particles are primary particles.

[0077] In this article, "primary particles" refer to particles that do not have obvious agglomeration interfaces in the particle scanning electron microscope image, but may have tiny pores and point or line defects, which are different from powder particles that are the smallest units without structures such as stacking and flocculation.

[0078] By making the primary average particle size of the first lithium iron phosphate salt particles 500nm-3000nm, the particles can be kept at a suitable micron-level size, thereby avoiding the interface side reactions and processing difficulties caused by nano-sizing the particles, and the particles will not be limited by excessive size and thus reduce the dynamic performance; in addition, it is beneficial to the stirring of the slurry containing the lithium iron phosphate salt particles and the increase of the solid content, thereby improving the processing problem of the battery cell and further increasing the volume energy density of the battery; in addition, it can avoid the normal deintercalation of lithium ions due to the excessive density of the carbon coating, thereby affecting the capacity of the battery cell.

[0079] When the positive electrode active material also includes the first lithium iron phosphate salt particles, and the primary average particle size s1 of the first lithium iron phosphate salt particles satisfies 500nm≤s1≤3000nm, by mixing part of the first lithium iron phosphate salt large particles into the manganese iron phosphate lithium iron salt material, tight stacking can be achieved. At the same time, since the large particle component is lithium iron phosphate salt, the kinetic properties of the material are better than those of large particles of manganese iron phosphate lithium iron salt. After the first lithium iron phosphate salt large particles crack during the cycle, since the particles do not contain manganese elements, the problems of electrolyte oxidation caused by the oxidizability of the corresponding material and the damage to the negative electrode SEI film caused by manganese dissolution will be alleviated, so that the secondary battery of the present application has a lower manganese dissolution amount, better high-temperature storage performance, better high-temperature cycle performance, and a higher positive electrode slurry solid content.

[0080] In some embodiments, the primary average particle size of the first lithium iron phosphate salt particles can be 250nm, 300nm, 350nm, 400nm, 440nm, 500nm, 550nm, 600nm, 650nm, 700nm, 730nm, 750nm, 780nm, 800nm, 830nm, 850nm, 870nm, 900nm, 950nm, 1000nm, 1100nm, 1200nm, 1300nm, 1400nm, 1500nm, 2000nm, 2100nm, 2200nm, 2300nm, 2400nm, 2500nm, 2600nm, 2700nm, 2800nm, 2900nm, 3000nm, 3500nm, 4000nm, or a range consisting of any two of the above primary average particle sizes or a value in the range.

[0081] In some embodiments, the primary average particle size s1 of the first lithium iron phosphate salt particles satisfies 500 nm≤s1≤3500 nm.

[0082] When the primary average particle size s1 of the first lithium iron phosphate salt particles satisfies 500nm≤s1≤3500nm, the secondary battery of the present application has lower manganese dissolution, better high-temperature storage performance, better high-temperature cycle performance, and higher positive electrode slurry solid content.

[0083] In some embodiments, the primary average particle size s1 of the first lithium iron phosphate salt particles satisfies 500 nm≤s1≤4000 nm.

[0084] When the primary average particle size s1 of the first lithium iron phosphate salt particles satisfies 500nm≤s1≤4000nm, the secondary battery of the present application has a lower manganese dissolution amount, better high-temperature storage performance, and a higher positive electrode slurry solid content.

[0085] In some embodiments, the primary average particle size s1 of the first lithium iron phosphate salt particles satisfies 300nm≤s1≤3500nm. In some embodiments, the primary average particle size s1 of the first lithium iron phosphate salt particles satisfies 500nm≤s1≤3000nm. In some embodiments, the primary average particle size s1 of the first lithium iron phosphate salt particles satisfies 650nm≤s1≤2500nm.

[0086] In some embodiments, the first lithium iron phosphate salt particles are single crystal particles and / or polycrystalline particles.

[0087] In the present application, the term "single crystal" refers to a crystal with a complete structure grown from a single crystal nucleus. The single crystal of the present application is a whole under the field of view of a transmission electron microscope photograph, and there is no grain boundary in the single crystal.

[0088] In some embodiments, the single crystal of the present application may have tiny defects, for example, micro-pores inside, a small number of points and surfaces, or a small number of particles adhering to each other on the surface of a particle.

[0089] In the present application, the term "polycrystalline" refers to a crystal composed of small single crystal particles randomly oriented and combined, and there are grain boundaries inside the polycrystalline.

[0090] In some embodiments, based on the total number of particles of the first lithium iron phosphate salt particles, the number of single crystal particles accounts for greater than or equal to 90%. When the number of single crystal particles is controlled within the above range, compared with polycrystalline and secondary agglomerates, the proportion of single crystal particles is higher, and the grain boundary has less barrier to lithium ions, which is conducive to further improving the transmission rate of lithium ions and improving the dynamic performance of the secondary battery.

[0091] The primary average particle size of the first lithium iron phosphate salt particles can be measured by methods and equipment known in the art. For example, it can be tested by scanning electron microscopy and long diameter statistical method. As an example, an argon ion beam is used to cut the pole piece perpendicular to the large surface of the positive electrode pole piece to expose the cross section, and the cross section is photographed by a scanning electron microscope. The boundary between the first positive electrode active layer and the second positive electrode active layer of the cross section is clear. The particle size of the positive electrode active layer containing the first lithium iron phosphate salt particles is statistically analyzed by the long diameter statistical method. Specifically, the total number of first lithium iron phosphate salt particles with a primary particle size greater than 80nm and the primary particle size and the first lithium iron phosphate salt particles with a primary particle size greater than 80nm can be counted in the electron microscope scanning photo. The primary average particle size of the first lithium iron phosphate salt particles = the primary particle size of the total first lithium iron phosphate salt particles / the total number of first lithium iron phosphate salt particles. In the primary particle size statistical process, particles with a primary particle size of 0 < ≤ 80nm are not within the statistical range.

[0092] In some embodiments, based on the total area of ​​the positive electrode active material in the cross section of the positive electrode sheet, the area of ​​the first lithium iron phosphate salt particles accounts for 2%-30%, and the area of ​​the lithium manganese iron phosphate salt particles accounts for 70%-98%.

[0093] In some embodiments, based on the total area of ​​the positive electrode active material in the cross section of the positive electrode sheet, the area ratio of the first lithium iron phosphate salt particles is 2-30%. In some embodiments, the area ratio of the first lithium iron phosphate salt particles is 2%, 23%, 25%, 30%, or a range consisting of any two of the above area ratios or a value within the range.

[0094] In some embodiments, based on the total area of ​​the positive electrode active material in the cross section of the positive electrode sheet, the area of ​​the manganese iron phosphate lithium salt particles accounts for 70%-98%. In some embodiments, the area of ​​the manganese iron phosphate lithium salt particles accounts for 65%, 70%, 72%, 74%, 75%, 97%, 98%.

[0095] The areas of the first lithium iron phosphate salt particles and the second lithium iron phosphate salt particles can be obtained by statistically analyzing the obtained scanning electron microscope images of the electrode cross-section using Avizo 3D software, and the corresponding area ratios can be obtained by dividing the areas of the first lithium iron phosphate salt particles by the total area.

[0096] In some embodiments, the positive electrode active material further includes second lithium iron phosphate salt particles, and the primary average particle size s2 of the second lithium iron phosphate salt particles satisfies 30 nm≤s2≤200 nm.

[0097] By adding a small amount of ultrafine particles to the positive electrode active material, the space utilization rate can be further improved. The ultrafine particles can be adjusted to the gap between the medium manganese iron phosphate lithium salt particles and the ultra-large lithium iron phosphate lithium salt particles, further improving the volume energy density, that is, further improving the compaction density of the pole piece. The ultrafine lithium iron phosphate will have a partial loss on the voltage platform compared to the ultrafine lithium iron phosphate manganese salt, but the gram capacity and surface stability have been greatly improved, especially the surface stability. It is difficult for the ultrafine lithium iron phosphate manganese salt material to form a good coating. In the charging state, the surface has a strong oxidizing property. At the same time, due to the Jiang Taylor effect, the superimposed small particles have a high specific surface energy, and the problem of manganese dissolution is prominent, which worsens the battery cycle life. The secondary battery of the present application controls the lithium iron phosphate manganese salt particles to have a relatively moderate particle size, contains less ultrafine powder and ultra-large particles, and the material shows a good cycle life and gram capacity. In addition, the secondary battery of the present application ensures a good compaction density by adding large particles of lithium iron phosphate and small particles of lithium iron phosphate materials to the positive electrode active material. For the positive electrode active material, through the deduction of the idealized dense packing model, in order to achieve a good compaction density, the material must have some large particles and ultrafine powder to form a dense packing, so as to achieve a good high-temperature cycle performance while having a high positive electrode sheet compaction density. When the positive electrode active material also includes a second lithium iron phosphate salt particle, and the primary average particle size s2 of the second lithium iron phosphate salt particle satisfies 30nm≤s2≤200nm, the secondary battery of the present application has a lower manganese dissolution amount, better high-temperature storage performance, and better high-temperature cycle performance.

[0098] In some embodiments, the positive electrode active material further includes second lithium iron phosphate salt particles, and the primary average particle size s2 of the second lithium iron phosphate salt particles satisfies 30 nm≤s2≤100 nm.

[0099] In some embodiments, the positive electrode active material also includes second lithium iron phosphate salt particles, and the primary average particle size of the second lithium iron phosphate salt particles can be 30nm, 40nm, 50nm, 60nm, 70nm, 80nm, 90nm, 100nm, 110nm, 120nm, 130nm, 140nm, 150nm, 160nm, 170nm, 180nm, 190nm, 200nm, or a range consisting of any two of the above primary average particle sizes or a value in the range.

[0100] The primary average particle size of the second lithium iron phosphate salt particles can be measured by methods and equipment known in the art. For example, it can be tested by scanning electron microscopy and long diameter statistical method. As an example, an argon ion beam is used to cut the pole piece perpendicular to the large surface of the positive pole piece to expose the cross section, and the cross section is photographed by a scanning electron microscope. The boundary between the second positive electrode active layer and the second positive electrode active layer of the cross section is clear. The particle size of the positive electrode active layer containing the second lithium iron phosphate salt particles is statistically analyzed by the long diameter statistical method. Specifically, the total number of second lithium iron phosphate salt particles with a primary particle size greater than 10nm and the primary particle size and of the second lithium iron phosphate salt particles with a primary particle size greater than 10nm can be counted in the electron microscope scanning photo. The primary average particle size of the second lithium iron phosphate salt particles = the primary particle size of the total second lithium iron phosphate salt particles / the total number of second lithium iron phosphate salt particles. In the primary particle size statistical process, particles with a primary particle size of 0 < ≤ 10nm are not within the statistical range.

[0101] In some embodiments, the primary average particle size of the lithium manganese iron phosphate salt particles is 150-210 nm, the primary average particle size s1 of the first lithium iron phosphate salt particles satisfies 870 nm ≤ s1 ≤ 3000 nm, and / or the primary average particle size s2 of the second lithium iron phosphate salt particles satisfies 60 nm ≤ s2 ≤ 200 nm.

[0102] In some embodiments, based on the total area of ​​the positive electrode active material in the cross section of the positive electrode sheet, the area of ​​the second lithium iron phosphate salt particles accounts for 1-10%; the area of ​​the first lithium iron phosphate salt particles accounts for 2-25%; the area of ​​the lithium manganese iron phosphate salt particles accounts for 70%-97%.

[0103] In some embodiments, based on the total area of ​​the positive electrode active material in the cross section of the positive electrode sheet, the area ratio of the second lithium iron phosphate salt particles is 1-10%. In some embodiments, based on the total area of ​​the positive electrode active material in the cross section of the positive electrode sheet, the area ratio of the second lithium iron phosphate salt particles is 1%, 3%, 5%, 10%, or a range consisting of any two of the above area ratios or a value within the range.

[0104] In some embodiments, based on the total area of ​​the positive active material in the cross section of the positive electrode sheet, the area of ​​the first lithium iron phosphate salt particles accounts for 2-25%. In some embodiments, based on the total area of ​​the positive active material in the cross section of the positive electrode sheet, the area of ​​the first lithium iron phosphate salt particles accounts for 2%, 23%, 25%, 30%, or a range consisting of any two of the above area ratios or a value in the range. In some embodiments, based on the total area of ​​the positive active material in the cross section of the positive electrode sheet, the area of ​​the first lithium iron phosphate salt particles accounts for 23-25%.

[0105] In some embodiments, based on the total area of ​​the positive active material in the cross section of the positive electrode sheet, the area of ​​the lithium iron manganese phosphate salt particles accounts for 70%-97%. In some embodiments, based on the total area of ​​the positive active material in the cross section of the positive electrode sheet, the area of ​​the lithium iron manganese phosphate salt particles accounts for 65%, 70%, 72%, 74%, 75%, 97%, 98%. In some embodiments, based on the total area of ​​the positive active material in the cross section of the positive electrode sheet, the area of ​​the lithium iron manganese phosphate salt particles accounts for 65%-74%.

[0106] The areas of the lithium iron manganese phosphate particles, the first lithium iron phosphate particles, and the second lithium iron phosphate particles can be obtained by statistically analyzing the obtained scanning electron microscope images of the electrode cross-section using Avizo 3D software, and the corresponding area ratio can be obtained by dividing the area of ​​each particle by the total area.

[0107] In some embodiments, the lithium manganese iron phosphate salt particles have a molecular formula Li m Fe x Mn r P y O j Q q , wherein Q comprises at least one of Al, Na, K, Mg, Cu, Cr, Zn, Pb, Ca, Co, Ni, Sr, Nb, V, Ti, B, S, Si, N, F, Cl, Br, 0.95≤m≤1.15, x>0, r>0, 0.9≤x+r≤1, 0.95≤y≤1, 3.5≤j≤4, 0≤q≤0.1, and / or

[0108] The first lithium iron phosphate salt particle has a molecular formula Li m1 Fe x1 P y1 O j1 Q1 q1, wherein Q1 includes at least one of Al, Na, K, Mg, Cu, Mn, Cr, Zn, Pb, Ca, Co, Ni, Sr, Nb, V, Ti, B, S, Si, N, F, Cl, Br, 0.95≤m1≤1.15, 0.9≤x1≤1, 0.95≤y1≤1, 3.5≤j1≤4, 0<q1≤0.1, and / or

[0109] The second lithium iron phosphate salt particle has a molecular formula Li m2 Fe x2 P y2 O j2 Q2 q2 , wherein Q2 includes at least one of Al, Na, K, Mg, Cu, Mn, Cr, Zn, Pb, Ca, Co, Ni, Sr, Nb, V, Ti, B, S, Si, N, F, Cl, and Br, 0.95≤m2≤1.15, 0.9≤x2≤1, 0.95≤y2≤1, 3.5≤j2≤4, and 0≤q2≤0.1.

[0110] In some embodiments, the lithium manganese iron phosphate salt particles have a molecular formula Li m Fe x Mn r P y O j Q q , where m can be 0.95, 0.98, 1.00, 1.03, 1.05, 1.08, 1.10, 1.13, 1.15, x+r can be 0.9, 1.0, y can be 0.95, 0.98, 1.00, 1.03, 1.05, 1.08, 1.10, 1.13, 1.15, j can be 3.5, 3.6, 3.7, 3.8, 3.9, 4, and q can be 0, 0.01, 0.02, 0.03, 0.04, 0.05, 0.06, 0.07, 0.08, 0.09, 0.1.

[0111] In some embodiments, the first lithium iron phosphate salt particles have a molecular formula of Li m1 Fe x1 P y1 O j1 Q q1, m1 can be 0.95, 0.98, 1.00, 1.03, 1.05, 1.08, 1.10, 1.13, 1.15, x1 can be 0.9, 1.0, y1 can be 0.95, 0.98, 1.00, 1.03, 1.05, 1.08, 1.10, 1.13, 1.15, j1 can be 3.5, 3.6, 3.7, 3.8, 3.9, 4, and q1 can be 0, 0.01, 0.02, 0.03, 0.04, 0.05, 0.06, 0.07, 0.08, 0.09, 0.1.

[0112] In some embodiments, the second lithium iron phosphate salt particles have a molecular formula of Li m2 Fe x2 P y2 O j2 Q q2 , m2 can be 0.95, 0.98, 1.00, 1.03, 1.05, 1.08, 1.10, 1.13, 1.15, x2 can be 0.9, 1.0, y2 can be 0.95, 0.98, 1.00, 1.03, 1.05, 1.08, 1.10, 1.13, 1.15, j2 can be 3.5, 3.6, 3.7, 3.8, 3.9, 4, and q2 can be 0, 0.01, 0.02, 0.03, 0.04, 0.05, 0.06, 0.07, 0.08, 0.09, 0.1.

[0113] Modifying the first lithium iron phosphate salt particles and / or the second lithium iron phosphate salt particles by Q1 and / or Q2 elements helps to improve the ion transport capacity of the positive electrode active material. The above elements can explain vacancies in the particle lattice or change the interatomic bond length, facilitate the movement of lithium ions in the lattice, thereby effectively improving the conductivity of the particles themselves and improving the kinetic properties of the positive electrode active material. In the present application, the modification can be specifically manifested as doping and / or coating.

[0114] In some embodiments, in the first lithium iron phosphate salt particles, Q1 includes at least one of Ti, V, Mg, and Nb, and the content of Ti, V, Mg, and / or Nb is 1000-10000 ppm based on the total weight of the first lithium iron phosphate salt particles.

[0115] In some embodiments, based on the total weight of the first lithium iron phosphate salt particles, the content of Q1 in the first lithium iron phosphate salt particles is 1000ppm, 2000ppm, 2500ppm, 3000ppm, 3500ppm, 4000ppm, 4500ppm, 5000ppm, 5500ppm, 6000ppm, 6500ppm, 7000ppm, 7500ppm, 8000ppm, 8500ppm, 9000ppm, 9500ppm, 10000ppm, or a range consisting of any two of the above Q1 contents or a value within the range.

[0116] The content of Q1 in the lithium iron phosphate salt particles, for example, the content of Ti, can be measured by methods and equipment known in the art. For example, the test can be performed with reference to GB / T 33822-2017.

[0117] The content of modifying elements in existing lithium iron phosphate salt particles is generally low or no modifying elements are added. Increasing the content of Q1 element in the first lithium iron phosphate salt particles helps to further improve the bulk ion transport capacity of the first lithium iron phosphate salt particles and improve its kinetic performance. However, as the content of Q1 element further increases, the bulk ion transport capacity may not continue to increase, and it may also occupy the position of lithium ions, affecting the performance of gram capacity. The range of Q1 element in this application helps to further obtain better kinetic performance and gram capacity.

[0118] In some embodiments, in the first lithium iron phosphate salt particles, Q1 includes Ti, and the content of Ti is 1000-10000 ppm, optionally 2500-6000 ppm, calculated based on the total weight of the first lithium iron phosphate salt particles.

[0119] In some embodiments, in the first lithium iron phosphate salt particles, Q1 includes V, and the content of V is 1000-10000 ppm, optionally 2500-6000 ppm, calculated based on the total weight of the first lithium iron phosphate salt particles.

[0120] In some embodiments, in the first lithium iron phosphate salt particles, Q1 includes Nb, and the content of Nb is 1000-10000 ppm, optionally 2500-6000 ppm, calculated based on the total weight of the first lithium iron phosphate salt particles.

[0121] Calculated based on the total weight of the first lithium iron phosphate salt particles, when the Ti content in the first lithium iron phosphate salt particles is 2500-6000ppm, by further appropriately increasing the Ti element content in the first lithium iron phosphate salt particles, it helps to further improve the bulk ion transport capacity of the first lithium iron phosphate salt particles, so that the secondary battery of the present application has better high-temperature storage performance and higher gram capacity.

[0122] In some embodiments, the specific surface area of ​​the first lithium iron phosphate salt particles is 3 m 2 / g-8m 2 / g.

[0123] In some embodiments, the specific surface area BET of the first lithium iron phosphate salt particles may be 3 m 2 / g, 3.5m 2 / g, 4m 2 / g, 4.5m 2 / g, 4.6m 2 / g, 5m 2 / g, 5.5m 2 / g, 6m 2 / g, 6.5m 2 / g, 7m 2 / g, 7.5m 2 / g, 8m 2 / g, 8.5m 2 / g, 9m 2 / g, 9.5m 2 / g, 10m 2 / g, 10.5m 2 / g, 11m 2 / g, 11.5m 2 / g, 12m 2 / g, or is a range of the specific surface area BET composition of any two of the above-mentioned first lithium iron phosphate salt particles or a value within the range.

[0124] In the present application, the term "specific surface area" or "BET" refers to the total area per unit mass of particles. In the present application, the BET of lithium iron phosphate particles is related to factors such as the primary average particle size of the lithium iron phosphate particles, the carbon content, the density of the carbon coating, the degree of fit between the carbon and the particles, and the looseness and porosity of the particles.

[0125] The BET specific surface area of ​​the particles can be measured by methods and equipment known in the art. For example, it can be tested according to the gas adsorption method with reference to GB / T 19587-2017. As an example, lithium iron phosphate particles are taken as samples and placed in a sample tube, the sample tube is immersed in liquid nitrogen at -196°C, and the adsorption amount of nitrogen on the solid surface at different pressures is measured at a relative pressure of 0.05-0.30. The sample monolayer adsorption amount is obtained based on the BET multilayer adsorption theory and its formula, thereby obtaining the specific surface area of ​​the sample.

[0126] If the BET of the first lithium iron phosphate salt particles is too high, the particles will absorb more water and affect the processing performance of the mixed positive electrode slurry. However, if the BET of the first lithium iron phosphate salt particles is too low, its gram capacity will be reduced. The BET of the first lithium iron phosphate salt particles is controlled at 3m 2 / g-8m 2 / g, which is conducive to further balancing the processing performance of the positive electrode slurry and the improvement of the solid content, thereby improving the processing problems of the battery cell and further increasing the volume energy density of the battery.

[0127] When the specific surface area of ​​the first lithium iron phosphate salt particles is 3m 2 / g-8m 2 / g, by introducing large particles with a smaller BET, the specific surface energy of the positive electrode active material can be reduced, the spontaneous agglomeration and polymerization of the material after the dispersion process can be slowed down, the viscosity of the slurry can be reduced, and a higher solid content can be achieved. At the same time, the reduction in the specific surface area of ​​the positive electrode active material and the corresponding reduction in the active reaction area can reduce the side reactions of the electrode under high voltage. The specific surface area of ​​the first lithium iron phosphate salt particles is relatively low, and the overall water absorption of the material can be reduced. The reduction in moisture reduces the side reactions of the battery during the charge and discharge process, so that the secondary battery of the present application has a lower manganese dissolution amount, a higher positive electrode slurry solid content, and a higher positive electrode sheet compaction density.

[0128] In some embodiments, the specific surface area of ​​the first lithium iron phosphate salt particles is 3 m 2 / g-6m 2 / g.

[0129] When the specific surface area (BET) of the first lithium iron phosphate salt particles is 3 m 2 / g-6m 2 / g, the secondary battery of the present application has good high-temperature storage performance, good high-temperature cycle performance, and high positive electrode sheet compaction density.

[0130] In some embodiments, the carbon content of the first lithium iron phosphate salt particles is Cx1 weight %, calculated based on the total weight of the first lithium iron phosphate salt particles, wherein 0.8≤Cx1≤2.0.

[0131] When 0.8≤Cx1≤2.0, the conductivity and coating integrity of the large-particle lithium iron phosphate salt material can be adjusted by controlling the carbon content of the large-particle lithium iron phosphate salt within a certain range. The higher the carbon content, the better the kinetic performance, the better the conductivity of the particles, the improved coating integrity, and the reduced side reactions on the surface of the material. However, too high a carbon content will lead to a high specific surface area of ​​the material, which will deteriorate the cycle performance. High carbon coating will lead to partial carbon redundancy in the form of floating carbon or ineffective coating, which will deteriorate the processing performance of the material, especially the solid content of the pulping of the material. The carbon content range of this application helps to further obtain better kinetic performance and processing performance.

[0132] In some embodiments, based on the total weight of the first lithium iron phosphate salt particles, the carbon content of the first lithium iron phosphate salt particles is 0.8 weight%, 0.9 weight%, 1.0 weight%, 1.1 weight%, 1.15 weight%, 1.2 weight%, 1.3 weight%, 1.4 weight%, 1.5 weight%, 1.6 weight%, 1.7 weight%, 1.8 weight%, 1.9 weight%, 2.0 weight%, or a range consisting of any two of the above carbon contents or a value within the range.

[0133] In some embodiments, the carbon content of the first lithium iron phosphate salt particles is Cx1 weight %, calculated based on the total weight of the first lithium iron phosphate salt particles, wherein 0.8≤Cx1≤1.2.

[0134] Calculated based on the total weight of the first lithium iron phosphate salt particles, the carbon content of the first lithium iron phosphate salt particles is Cx1 weight %, when 0.8≤Cx1≤1.2, the secondary battery of the present application has better high-temperature storage performance, lower manganese dissolution, higher positive electrode slurry solid content, better high-temperature cycle performance, and higher positive electrode sheet compaction density.

[0135] In some embodiments, the carbon contained in the first lithium iron phosphate salt particles is coated on the surface of the particles. In some embodiments, the carbon contained in the first lithium iron phosphate salt particles is embedded in the particles. In some embodiments, the carbon contained in the first lithium iron phosphate salt particles is partially coated on the surface of the particles and partially embedded in the particles.

[0136] In some embodiments, the ratio z1 of the specific surface area of ​​the first lithium iron phosphate salt particle to Cx1 satisfies 1.5≤z1≤8.5. In some embodiments, the ratio z1 of the specific surface area of ​​the first lithium iron phosphate salt particle to Cx1 satisfies 3≤z1≤6.

[0137] In some embodiments, z1 can be 1.5, 1.8, 2, 2.3, 2.5, 2.8, 3, 3.2, 3.5, 3.75, 3.8, 4, 4.2, 4.3, 4.5, 4.58, 4.8, 4.98, 5, 5.3, 5.42, 5.5, 5.71, 5.8, 5.83, 6, 6.3, 6.5, 6.7, 6.8, 7, 7.3, 7.5, 7.8, 7.9, 8, 8.3, 8.5, 8.6, or a range consisting of any two of the above z1 values ​​or a value within the range.

[0138] The ratio z1 of the specific surface area BET of the first lithium iron phosphate salt particle to Cx1 can characterize the uniform density of the carbon contained in the first lithium iron phosphate salt particle. When the primary average particle size and carbon content of the first lithium iron phosphate salt particle remain unchanged, the lower the ratio z1, the higher the carbon coating utilization rate in the particle, the less floating carbon, and the more uniform and dense the carbon contained in the first lithium iron phosphate salt particle. Improving the uniform density of the contained carbon is conducive to further improving the kinetic performance and gram capacity of the first lithium iron phosphate salt particle, but too high carbon density may affect the insertion and extraction of lithium ions, and to a certain extent affect the kinetic performance and gram capacity of the secondary battery. The range of the ratio z1 of the present application is conducive to the carbon contained in the first lithium iron phosphate salt particle having a suitable uniform density, which is conducive to improving the conductivity of the particle surface, and is conducive to further improving the gram capacity and kinetic performance of the secondary battery.

[0139] In some embodiments, a ratio z1 of the specific surface area of ​​the first lithium iron phosphate salt particles to Cx1 satisfies 3.8≤z1≤5.

[0140] When the ratio z1 of the specific surface area of ​​the first lithium iron phosphate salt particles to Cx1 satisfies 3.8≤z1≤5, the secondary battery of the present application has better high-temperature storage performance, lower manganese dissolution, higher positive electrode slurry solid content, better high-temperature cycle performance, and higher positive electrode sheet compaction density.

[0141] In some embodiments, the capacity ratio of the first lithium iron phosphate salt particles is η≥88%, where η is defined as:

[0142] A battery using the first lithium iron phosphate salt particles as the positive electrode active material is charged and discharged twice at a constant current rate of 0.1C in the voltage range of 2.0V to 3.75V, and then charged and discharged once at a constant current rate of 1C. In the charge and discharge test at a rate of 1C, the capacity value at a discharge voltage of 3.2V is extracted as C1, and the capacity value at a discharge voltage of 2.0V is extracted as C2, η=C1 / C2, wherein the charging process includes constant voltage charging, a constant voltage of 3.75V, and a constant voltage cut-off current of 50μA.

[0143] In some embodiments, n can be 88%, 88.1%, 89%, 90%, 90.1%, 91%, 92%, 92.2%, 93%, 94%, 94.1%, 94.5%, 95%, 95.1%, or a range consisting of any two of the above n values ​​or a value within the range.

[0144] The η value of the first lithium iron phosphate salt particles can be measured by methods and equipment known in the art. As an example, a button battery is first prepared. The specific button battery preparation process is: 2.0000g of the first lithium iron phosphate salt particles are mixed with 0.1111g of conductive carbon black and 0.1111g of polyvinylidene fluoride, and then added to 2.5g of organic solvent N-methylpyrrolidone, and mixed thoroughly to form a slurry. The slurry is coated on aluminum foil with a coating thickness of 140 microns, vacuum dried at 120°C for 2h, and punched into a disc with a diameter of 13mm using a puncher. Use a tablet press to press the tablet at 10Mpa, and vacuum insulate at 120°C for 12h to obtain a positive electrode. Weigh the weight of the positive electrode, where the loading amount of the lithium iron phosphate salt particles is 11-12mg. Button cells were assembled in an argon-protected glove box, with a metal lithium sheet as the negative electrode, an electrolyte of a 1:1 volume ratio of EC (ethylene carbonate) and DMC (1,2-dimethyl carbonate) mixed solvent, LiPF6 electrolyte, and a Celgard 2400 microporous polyethylene membrane as the separator.

[0145] The prepared button cell was tested for electrical performance on a blue electric tester. Specifically, the button cell was charged and discharged twice at a constant current of 0.1C within a voltage range of 2.0V to 3.75V, and then charged and discharged once at a constant current of 1C. In the charge and discharge test at a rate of 1C, the capacity value extracted when the discharge voltage was 3.2V was recorded as C1, and the capacity value extracted when discharged to 2.0V was recorded as C2, and η = C1 / C2. The charging process includes constant voltage charging, constant voltage of 3.75V, and constant voltage cut-off current of 50μA.

[0146] The capacity ratio η of the first lithium iron phosphate salt particles can reflect its kinetic performance and platform retention performance, which can be adjusted by adjusting the primary average particle size, carbon content, carbon source and carbon film-forming agent ratio, modifier and its content of the first lithium iron phosphate salt particles. The η value of the first lithium iron phosphate salt particles of the present application is ≥88%, which has good kinetic performance. At the same time, when the η value is high, the secondary battery can still maintain good power performance when discharged to a low state of charge (SOC), that is, the battery with a high η value has a small voltage drop value when discharged at a low power and high current.

[0147] In some embodiments, the aspect ratio of the second lithium iron phosphate salt particles is ≥ 1.1. In some embodiments, the aspect ratio of the second lithium iron phosphate salt particles is ≥ 1.3.

[0148] When the aspect ratio of the second lithium iron phosphate salt particles is ≥1.3, the material has good crystallinity, so that the secondary battery of the present application has good high-temperature storage performance, lower manganese dissolution, better high-temperature cycle performance, and higher gram capacity.

[0149] In the present application, the term "aspect ratio" refers to the ratio of the diameter of a primary particle in the long axis direction to the diameter in the short axis direction. Assuming the diameter in the long axis direction is a, and the diameter in the short axis direction is b, the aspect ratio = a / b; this parameter is often used to describe the morphology of particles and can be used to measure their sphericity.

[0150] The aspect ratio of the second lithium iron phosphate salt particles can be measured by methods and equipment known in the art. For example, it can be tested by the following method: take the cold-pressed pole piece, cut the pole piece perpendicular to the large surface direction of the pole piece by an Ar particle beam, expose the end face, and obtain an image by scanning electron microscope. Then analyze the scanning electron microscope image of the pole piece section by image software, measure the long diameter a and short diameter b of the particle, and obtain their ratio, which is the aspect ratio of the particle.

[0151] In some embodiments, the ratio of the diffraction peak intensity of the (020) crystal plane of the second lithium iron phosphate salt particle to the diffraction peak intensity of the (211) crystal plane W is greater than or equal to 0.98. In some embodiments, the ratio of the diffraction peak intensity of the (020) crystal plane of the second lithium iron phosphate salt particle to the diffraction peak intensity of the (211) crystal plane W is greater than or equal to 1.03. In some embodiments, the ratio of the diffraction peak intensity of the (020) crystal plane of the second lithium iron phosphate salt particle to the diffraction peak intensity of the (211) crystal plane W is greater than or equal to 1.08.

[0152] When the ratio of the diffraction peak intensity of the (020) crystal plane to the diffraction peak intensity of the (211) crystal plane of the second lithium iron phosphate salt particles is W ≥ 1.03, the material has good crystallinity; in addition, a higher W value indicates that the (020) crystal plane is more exposed, which is more conducive to the deintercalation of lithium ions, so that the secondary battery of the present application has better high-temperature storage performance, lower manganese dissolution, better high-temperature cycle performance, and higher gram capacity.

[0153] The ratio W of the (020) crystal plane diffraction peak intensity to the (211) crystal plane diffraction peak intensity can be measured by methods and equipment known in the art. For example, it can be tested by the following method:

[0154] The diffraction peak intensity ratio of the second lithium iron phosphate salt particles was tested by X-rays. The second lithium iron phosphate salt particles were placed on the test platform of the X-ray diffractometer (model: Shimadzu XRD-7000) using a copper target X-ray diffractometer. The starting angle of the scan was 10°, the ending angle was 90°, the step length was 0.013, and then the test was started to obtain the diffraction pattern of the second lithium iron phosphate salt particles in the diffraction angle range of 10° to 90°. The ratio W of the diffraction peak intensity of the (020) crystal plane to the diffraction peak intensity of the (211) crystal plane was determined based on the diffraction pattern.

[0155] In some embodiments, the specific surface area of ​​the second lithium iron phosphate salt particles is 11 m 2 / g-14m 2 In some embodiments, the specific surface area of ​​the second lithium iron phosphate salt particles is 11 m 2 / g-12m 2 In some embodiments, the specific surface area of ​​the second lithium iron phosphate salt particles is 12 m 2 / g-14m 2 / g.

[0156] In some embodiments, based on the total weight of the second lithium iron phosphate salt particles, the carbon content of the second lithium iron phosphate salt particles is Cx2 weight %, and the ratio z2 of the specific surface area of ​​the second lithium iron phosphate salt particles to Cx2 satisfies 8≤z2≤11. In some embodiments, 8.1≤z2≤10.4. In some embodiments, based on the total weight of the second lithium iron phosphate salt particles, the carbon content of the second lithium iron phosphate salt particles is Cx2 weight %, and the ratio z2 of the specific surface area of ​​the second lithium iron phosphate salt particles to Cx2 is 8.1, 8.9, 10.4, or the range composed of any two of the above z2 or the value in the range.

[0157] In some embodiments, the carbon contained in the second lithium iron phosphate salt particles is coated on the surface of the particles. In some embodiments, the carbon contained in the second lithium iron phosphate salt particles is embedded in the particles. In some embodiments, the carbon contained in the second lithium iron phosphate salt particles is partially coated on the surface of the particles and partially embedded in the particles.

[0158] In some embodiments, the specific surface area of ​​the lithium manganese iron phosphate particles is 8-20 m 2 In some embodiments, the specific surface area of ​​the lithium manganese iron phosphate particles is 10-20 m 2 / g.

[0159] In some embodiments, the specific surface area of ​​the lithium manganese iron phosphate particles is 8 m 2 / g, 9m 2 / g, 10m 2 / g, 10.5m 2 / g, 11m 2 / g, 12m 2 / g, 13m 2 / g, 14m 2 / g, 15m 2 / g, 16m 2 / g, 17m 2 / g, 18m 2 / g, 19m 2 / g, 20m 2 / g, or a range consisting of any two of the above specific surface areas or a value within the range.

[0160] In some embodiments, the specific surface area of ​​the lithium manganese iron phosphate particles is 10-18m 2 In some embodiments, the specific surface area of ​​the lithium manganese iron phosphate particles is 10-17m 2 / g.

[0161] When the specific surface area of ​​lithium manganese iron phosphate particles is 10m 2 / g-17m 2 / g, the secondary battery of the embodiment of the present application has better high-temperature storage performance, lower manganese dissolution, better high-temperature cycle performance, and higher positive electrode sheet compaction density.

[0162] In some embodiments, the carbon content of the lithium iron manganese phosphate salt particles is Cx weight %, calculated based on the total weight of the lithium iron manganese phosphate salt particles, wherein 1.2≤Cx≤1.8.

[0163] In some embodiments, the carbon content of the lithium manganese iron phosphate salt particles is Cx weight %, calculated based on the total weight of the lithium manganese iron phosphate salt particles, wherein Cx is 1.2, 1.3, 1.4, 1.5, 1.6, 1.65, 1.7, 1.8, or a range consisting of any two of the above Cx or a value within the range.

[0164] In some embodiments, the carbon contained in the lithium iron manganese phosphate salt particles is coated on the surface of the particles. In some embodiments, the carbon contained in the lithium iron manganese phosphate salt particles is embedded in the particles. In some embodiments, the carbon contained in the lithium iron manganese phosphate salt particles is partially coated on the surface of the particles and partially embedded in the particles.

[0165] In some embodiments, the ratio z of the specific surface area of ​​the lithium manganese iron phosphate salt particles to Cx satisfies 7≤z≤13. In some embodiments, the ratio z of the specific surface area of ​​the lithium manganese iron phosphate salt particles to Cx satisfies 7.1≤z≤12.5. In some embodiments, the ratio z of the specific surface area of ​​the lithium manganese iron phosphate salt particles to Cx is 7, 7.1, 7.3, 7.5, 7.6, 7.9, 8.3, 8.6, 8.8, 9.1, 9.3, 9.4, 12.5, 13, or a range consisting of any two of the above z or a value in the range.

[0166] In some embodiments, the first lithium iron phosphate salt particles satisfy at least one of (a)-(f):

[0167] (a) Dv10 of the first lithium iron phosphate salt particles is ≥ 0.2 μm;

[0168] (b) the Dv50 of the first lithium iron phosphate particles is 0.5-5 μm;

[0169] (c) Dv90 of the first lithium iron phosphate salt particles is ≤10 μm;

[0170] (d) Dv99 of the first lithium iron phosphate salt particles is ≤12 μm;

[0171] (e) The powder compaction density of the first lithium iron phosphate salt under a pressure of 3 tons is ≥ 2.25 g / cm 3 ;

[0172] (f) The powder resistivity of the first lithium iron phosphate salt is less than 60Ω·cm.

[0173] In the present application, the term "Dv10" refers to the particle size corresponding to when the volume cumulative particle size distribution percentage in the particles reaches 10%.

[0174] In the present application, the term "Dv90" refers to the particle size corresponding to when the volume cumulative particle size distribution percentage in the particles reaches 90%.

[0175] In the present application, the term "Dv99" refers to the particle size corresponding to when the volume cumulative particle size distribution percentage in the particles reaches 99%.

[0176] In this application, the term "powder compaction density" refers to the density of a compact with a certain density and strength formed when the powder moves and deforms during the external compression process, larger gaps are filled, the contact area between particles increases, the attraction between atoms is generated, and the mechanical fit between particles is enhanced. The unit is g / cm 3 .

[0177] In some embodiments, the first lithium iron phosphate salt particles have a Dv10<Dv50.

[0178] In some embodiments, the first lithium iron phosphate salt particles have a Dv90>Dv50.

[0179] In some embodiments, the Dv50 of the first lithium iron phosphate particles can be 500nm, 600nm, 700nm, 800nm, 900nm, 1000nm, 1100nm, 1200nm, 1300nm, 1400nm, 1500nm, 1700nm, 1900nm, 2000nm, 2300nm, 2500nm, 2700nm, 2900nm, 3000nm, 3200nm, 3400nm, 3600nm, 3800nm, 4000nm, 4200nm, 4400nm, 4600nm, 4800nm, 5000nm, or a range composed of the Dv50 of any two of the above second crushing products or a value within this range.

[0180] The Dv10, Dv50, Dv90 and Dv99 of the first lithium iron phosphate salt particles can be measured by methods and equipment known in the art. For example, it can be measured with reference to GB / T19077.1-2016 using a laser particle size analyzer (Malvern MasterSize 3000).

[0181] Under different pressures, the powder compaction density of the first lithium iron phosphate salt particles can be measured by methods and equipment known in the art. For example, it can be measured by using a compaction density instrument with reference to GB / T 24533-2009. Specifically, a certain amount of lithium iron phosphate salt particles are placed on a special compaction mold (the mold diameter is known), and the mold is hollow in the middle and has a metal disc above and below. The lithium iron phosphate salt particles are placed between the metal discs, a metal cylinder is placed on the top, and the mold is placed on the compaction density instrument. Different pressures (for example, 3T) can be set. The thickness of the lithium iron phosphate salt particles under different pressures can be read on the device. The powder compaction density of the lithium iron phosphate salt particles is ρ=m / v, where v=(S×H), m is the mass of the lithium iron phosphate salt particles, S is the bottom area of ​​the mold, and H is the thickness of the lithium iron phosphate salt particles after compaction.

[0182] The powder resistivity of the first lithium iron phosphate salt particles can be measured by methods and equipment known in the art. For example, GB / T 33822-2017 can be referred to and a powder resistivity meter (Suzhou Jingge, ST2722 model) can be used for measurement. Specifically, a certain amount of lithium iron phosphate salt particles (for example, 1 g) is weighed and added to the feeding chamber of the powder resistivity meter, and a pressure of 8 MPa is applied to test the forward resistivity and reverse resistivity of the lithium iron phosphate salt particles respectively, and the average value of the two is taken as the powder resistivity of the lithium iron phosphate salt particles.

[0183] By making the first lithium iron phosphate salt particles satisfy at least one of (a)-(f), the first lithium iron phosphate salt particles can better achieve the technical effect of the present application.

[0184] In some embodiments, the first lithium iron phosphate salt particles are mainly obtained by the following preparation method:

[0185] Providing a raw material containing at least a lithium source, an iron source, a phosphorus source, optionally a carbon film-forming agent, optionally a carbon source, and optionally a modifier, and performing at least two sintering steps, wherein:

[0186] The temperature of the first sintering is 500℃-760℃, and can be 550℃-720℃;

[0187] The temperature of the second sintering is 700°C-800°C, and can be optionally 720°C-780°C.

[0188] In some embodiments, the temperature of the first sintering may be 500°C, 530°C, 550°C, 580°C, 600°C, 630°C, 650°C, 680°C, 700°C, 710°C, 720°C, 730°C, 740°C, 750°C, 760°C, or a range consisting of any two of the above first sintering temperatures or a value in this range; the temperature of the second sintering may be 700°C, 710°C, 720°C, 730°C, 740°C, 750°C, 760°C, 770°C, 780°C, 790°C, 800°C, or a range consisting of any two of the above second sintering temperatures or a value in this range.

[0189] In some embodiments, the heating rates of the first sintering and the second sintering are independently 2° C. / min-20° C. / min.

[0190] In some embodiments, the heating rates in the first sintering and the second sintering are each independently 2°C / min, 5°C / min, 7°C / min, 10°C / min, 13°C / min, 15°C / min, 17°C / min or 20°C / min.

[0191] In some embodiments, the constant temperature sintering time of the first sintering is 1-6 hours. In some embodiments, the constant temperature sintering time of the first sintering can be 1 hour, 1.5 hours, 2 hours, 2.5 hours, 3 hours, 3.5 hours, 4 hours, 4.5 hours, 5 hours, 5.5 hours or 6 hours.

[0192] In some embodiments, the constant temperature sintering time of the second sintering is 2-12 hours. In some embodiments, the constant temperature sintering time of the second sintering can be 1 hour, 1.5 hours, 2 hours, 2.5 hours, 3 hours, 3.5 hours, 4 hours, 4.5 hours, 5 hours, 5.5 hours, 6 hours, 6.5 hours, 7 hours, 7.5 hours, 8 hours, 8.5 hours, 9 hours, 9.5 hours, 10 hours, 10.5 hours, 11 hours, 11.5 hours or 12 hours.

[0193] Compared to the traditional preparation method that uses high temperature to achieve particle growth, the first lithium iron phosphate salt particles of the embodiment of the present application are sintered twice, and controlling the temperature of the two sinterings is conducive to preparing the first lithium iron phosphate salt particles having the primary average particle size and specific surface area of ​​the present application. Furthermore, controlling the heating rate, sintering temperature and constant temperature sintering time of the first sintering and / or the second sintering helps to reduce side reactions, thereby better preparing the first lithium iron phosphate salt particles of the present application. Furthermore, in the conventional high-temperature sintering process, the carbon coating layer on the surface of the particles is prone to cracking, reducing the integrity of the carbon coating. The present application performs large particle synthesis at low temperature, which is conducive to improving the consistency and uniformity of the surface carbon coating.

[0194] In some embodiments, the first lithium iron phosphate salt particles are mainly obtained by the following preparation method:

[0195] Providing raw materials containing at least a lithium source, an iron source, a phosphorus source, a carbon source, a carbon film-forming agent, and a modifier, and performing at least two sintering steps, wherein:

[0196] The carbon content of the material after the first sintering is 0.01 wt%-0.79 wt%, optionally 0.05 wt%-0.4 wt%;

[0197] The carbon content of the material after the second sintering is 0.8 wt % to 2.0 wt %, and can be optionally 1.0 wt % to 1.6 wt %.

[0198] In some embodiments, the carbon content of the material after the first sintering can be 0.01 weight%, 0.05 weight%, 0.1 weight%, 0.15 weight%, 0.20 weight%, 0.25 weight%, 0.30 weight%, 0.35 weight%, 0.40 weight%, 0.45 weight%, 0.50 weight%, 0.55 weight%, 0.60 weight%, 0.65 weight%, 0.70 weight%, 0.75 weight%, 0.79 weight, or a range consisting of any two of the above carbon contents or a value in this range; the carbon content of the material after the second sintering can be 0.8 weight%, 0.9 weight%, 1.0 weight%, 1.1 weight%, 1.2 weight%, 1.3 weight%, 1.4 weight%, 1.5 weight%, 1.6 weight%, 1.7 weight%, 1.8 weight%, 1.9 weight%, 2.0 weight, or a range consisting of any two of the above carbon contents or a value in this range.

[0199] In the preparation method of the embodiment of the present application, adding a carbon source before the first sintering can effectively reduce the trivalent iron in the raw material, thereby improving the purity and stability of the product. Further, by controlling the temperature of the first sintering and the carbon content of the intermediate after the first sintering within the above range, it is helpful to increase the primary particle size of the first lithium iron phosphate salt particle precursor obtained after the first sintering. Specifically, during the first sintering process, the lower carbon content is conducive to reducing the barrier effect of the carbon layer on the growth process of the first lithium iron phosphate particles, which is conducive to the crystal growth of the first lithium iron phosphate salt particle precursor at a lower temperature. At the same time, it is also conducive to the solid-phase diffusion reaction between the modifier that may be added and the first lithium iron phosphate salt material, thereby facilitating the modification of metal ions at a higher concentration. By controlling the temperature of the second sintering and the carbon content of the sintered material within the above range, it is helpful to better coat the carbon on the surface of the first lithium iron phosphate salt particles to form a uniform and dense carbon coating layer, which is conducive to improving the surface conductivity of the first lithium iron phosphate particles, and improving its kinetic properties and gram capacity.

[0200] In some embodiments, a raw material containing at least a lithium source, an iron source, a phosphorus source, a carbon source, a modifier, and a carbon film-forming agent is provided, and sintering is performed at least twice.

[0201] In some embodiments, the mixing ratio of the lithium source, the iron source, and the phosphorus source satisfies, based on the atomic mole number of each element, Fe:P=(0.96-0.985):1, Li:Fe=(1.0-0.95):1.1.

[0202] In some embodiments, the mixing ratio of the iron source and the phosphorus source, calculated on the basis of the atomic moles of each element, satisfies Fe:P=0.96:1, Fe:P=0.965:1, Fe:P=0.97:1, Fe:P=0.975:1, Fe:P=0.98:1 or Fe:P=0.985:1.

[0203] In some embodiments, the mixing ratio of the lithium source and the iron source, calculated on the basis of the atomic moles of each element, satisfies Li:Fe=1.0:1.1, Li:Fe=0.99:1.1, Li:Fe=0.98:1.1, Li:Fe=0.97:1.1, Li:Fe=0.96:1.1 or Li:Fe=0.95:1.1.

[0204] In some embodiments, the weight ratio of the carbon source to the carbon film-forming agent is (9-0.25): 1. In some embodiments, the weight ratio of the carbon source to the carbon film-forming agent may be 9:1, 8:1, 7:1, 6:1, 5:1, 4:1, 3:1, 2:1, 1:1, 0.8:1, 0.5:1 or 0.25:1.

[0205] In some embodiments, the lithium source is a lithium-containing compound. In some embodiments, the lithium source includes at least one of lithium dihydrogen phosphate, lithium oxalate, lithium carbonate, lithium oxide, lithium hydroxide, and lithium acetate. In some embodiments, the lithium source includes lithium carbonate.

[0206] In some embodiments, the iron source is an iron-containing compound. In some embodiments, the iron source includes at least one of ferric hydroxide, ferrous chloride, ferric oxide, ferric phosphate, ferric pyrophosphate, ferrous oxalate, iron powder, ferric nitrate, ferric oxide, and ferric oxyhydroxide. In some embodiments, the iron source includes ferric oxide.

[0207] In some embodiments, the phosphorus source is a phosphoric acid compound. In some embodiments, the phosphorus source includes at least one of phosphoric acid, ammonium dihydrogen phosphate, and diammonium hydrogen phosphate. In some embodiments, the phosphorus source includes phosphoric acid.

[0208] In some embodiments, the carbon source comprises at least one of citric acid, glucose, sucrose, starch, fructose, and lactose. In some embodiments, the carbon source comprises glucose.

[0209] In some embodiments, the carbon film-forming agent includes at least one of polyethylene glycol, polyaniline, polyacrylonitrile, polyvinyl pyrrolidone, and polyvinyl alcohol. In some embodiments, the carbon film-forming agent includes polyaniline.

[0210] In some embodiments, the modifier includes at least one of titanium dioxide, vanadium pentoxide, n-butyl titanate, ammonium metavanadate, niobium ethoxide, niobium oxalate, niobium pentoxide, magnesium hydroxide, and magnesium nitrate. In some embodiments, the modifier includes titanium dioxide.

[0211] By using the raw materials in the above ratio, it is advantageous to form the first lithium iron phosphate salt particles of the present application.

[0212] In some embodiments, the method for preparing the first lithium iron phosphate salt particles comprises the following steps:

[0213] The first pulverization is performed after the first sintering, and the second pulverization is performed after the second sintering, wherein:

[0214] The Dv50 of the product after the first pulverization is 300nm-1200nm, and can be optionally 400nm-1100nm;

[0215] The Dv50 of the product after the second pulverization is 500nm-5000nm, and can be optionally 700nm-2500nm.

[0216] In the present application, the term "Dv50" refers to the particle size corresponding to when the volume cumulative particle size distribution percentage in the particles reaches 50%.

[0217] In some embodiments, the Dv50 of the product after the first crushing can be 300nm, 400nm, 500nm, 600nm, 700nm, 800nm, 900nm, 1000nm, 1100nm, 1200nm, or a range consisting of the Dv50 of any two of the above products after the first crushing or a value within the range.

[0218] In some embodiments, the Dv50 of the product after the second crushing can be 500nm, 600nm, 700nm, 800nm, 900nm, 1000nm, 1100nm, 1200nm, 1300nm, 1400nm, 1500nm, 1700nm, 1900nm, 2000nm, 2300nm, 2500nm, 2700nm, 2900nm, 3000nm, 3200nm, 3400nm, 3600nm, 3800nm, 4000nm, 4200nm, 4400nm, 4600nm, 4800nm, 5000nm, or a range composed of the Dv50 of any two of the above products after the second crushing, or a value in this range.

[0219] In some embodiments, the pulverization includes one or more of mechanical crushing, grinding, sand milling, and air flow crushing.

[0220] The Dv50 of the particles can be measured using methods and equipment commonly used in the art. As an example, it can be measured using a laser particle size analyzer (Malvern Master Size 3000) with reference to GB / T19077.1-2016.

[0221] Controlling the Dv50 of the product after the first pulverization within the above range is conducive to reducing the growth barrier effect of the added carbon source and the possibly added modifying elements on the first lithium iron phosphate salt particle precursor crystal, and is helpful to prepare a micron-sized lithium iron phosphate salt particle precursor. By controlling the Dv50 value of the product after the second pulverization within the above range, it is helpful to obtain the first lithium iron phosphate salt particles having the primary average particle size of the present application.

[0222] A second aspect of the present application provides an electric device, which includes the secondary battery according to the first aspect of the present application.

[0223] In addition, the secondary battery and the electric device of the present application will be described below with reference to the drawings as appropriate.

[0224] In one embodiment of the present application, a secondary battery is provided.

[0225] Generally, a secondary battery includes a positive electrode sheet, a negative electrode sheet, an electrolyte and a separator. During the battery charging and discharging process, active ions are embedded and released back and forth between the positive electrode sheet and the negative electrode sheet. The electrolyte plays the role of conducting ions between the positive electrode sheet and the negative electrode sheet. The separator is set between the positive electrode sheet and the negative electrode sheet, mainly to prevent the positive and negative electrodes from short-circuiting, while allowing ions to pass through.

[0226] [Positive electrode]

[0227] The positive electrode plate includes a positive electrode current collector and a positive electrode film layer arranged on at least one surface of the positive electrode current collector, wherein the positive electrode film layer includes the positive electrode active material of the first aspect of the present application.

[0228] As an example, the positive electrode current collector has two surfaces opposite to each other in its thickness direction, and the positive electrode film layer is disposed on any one or both of the two opposite surfaces of the positive electrode current collector.

[0229] In some embodiments, the positive electrode current collector may be a metal foil or a composite current collector. For example, aluminum foil may be used as the metal foil. The composite current collector may include a polymer material base and a metal layer formed on at least one surface of the polymer material base. The composite current collector may be formed by forming a metal material (aluminum, aluminum alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy, etc.) on a polymer material substrate (such as a substrate of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE), etc.).

[0230] In some embodiments, the positive electrode film layer may further optionally include a binder. As an example, the binder may include at least one of polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), vinylidene fluoride-tetrafluoroethylene-propylene terpolymer, vinylidene fluoride-hexafluoropropylene-tetrafluoroethylene terpolymer, tetrafluoroethylene-hexafluoropropylene copolymer, and fluorine-containing acrylate resin.

[0231] In some embodiments, the positive electrode film layer may further include a conductive agent, which may include, for example, at least one of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers.

[0232] In some embodiments, the positive electrode sheet can be prepared in the following manner: the components for preparing the positive electrode sheet, such as the positive electrode active material, the conductive agent, the binder and any other components are dispersed in a solvent (such as N-methylpyrrolidone) to form a positive electrode slurry; the positive electrode slurry is coated on the positive electrode collector, and after drying, cold pressing and other processes, the positive electrode sheet can be obtained.

[0233] [Negative electrode]

[0234] The negative electrode sheet includes a negative electrode current collector and a negative electrode film layer disposed on at least one surface of the negative electrode current collector, wherein the negative electrode film layer includes a negative electrode active material.

[0235] As an example, the negative electrode current collector has two surfaces opposite to each other in its thickness direction, and the negative electrode film layer is disposed on any one or both of the two opposite surfaces of the negative electrode current collector.

[0236] In some embodiments, the negative electrode current collector may be a metal foil or a composite current collector. For example, as the metal foil, copper foil may be used. The composite current collector may include a polymer material base layer and a metal layer formed on at least one surface of the polymer material substrate. The composite current collector may be formed by forming a metal material (copper, copper alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy, etc.) on a polymer material substrate (such as a substrate of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE), etc.).

[0237] In some embodiments, the negative electrode active material may adopt the negative electrode active material for the battery known in the art. As an example, the negative electrode active material may include at least one of the following materials: artificial graphite, natural graphite, soft carbon, hard carbon, silicon-based materials, tin-based materials, lithium titanate, etc. The silicon-based material may be selected from at least one of elemental silicon, silicon oxide compounds, silicon-carbon composites, silicon-nitrogen composites, and silicon alloys. The tin-based material may be selected from at least one of elemental tin, tin oxide compounds, and tin alloys. However, the present application is not limited to these materials, and other traditional materials that can be used as negative electrode active materials for batteries may also be used. These negative electrode active materials may be used alone or in combination of two or more.

[0238] In some embodiments, the negative electrode film layer may further include a binder. The binder may be selected from at least one of styrene-butadiene rubber (SBR), polyacrylic acid (PAA), sodium polyacrylate (PAAS), polyacrylamide (PAM), polyvinyl alcohol (PVA), sodium alginate (SA), polymethacrylic acid (PMAA) and carboxymethyl chitosan (CMCS).

[0239] In some embodiments, the negative electrode film layer may further include a conductive agent, which may be selected from at least one of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene and carbon nanofibers.

[0240] In some embodiments, the negative electrode film layer may optionally include other additives, such as a thickener (eg, sodium carboxymethyl cellulose (CMC-Na)).

[0241] In some embodiments, the negative electrode sheet can be prepared in the following manner: the components for preparing the negative electrode sheet, such as the negative electrode active material, the conductive agent, the binder and any other components are dispersed in a solvent (such as deionized water) to form a negative electrode slurry; the negative electrode slurry is coated on the negative electrode collector, and after drying, cold pressing and other processes, the negative electrode sheet can be obtained.

[0242] [Electrolytes]

[0243] The electrolyte plays the role of conducting ions between the positive electrode and the negative electrode. The present application has no specific restrictions on the type of electrolyte, which can be selected according to needs. For example, the electrolyte can be liquid, gel or all-solid.

[0244] In some embodiments, the electrolyte is an electrolyte solution, which includes an electrolyte salt and a solvent.

[0245] In some embodiments, the electrolyte salt can be selected from at least one of lithium hexafluorophosphate, lithium tetrafluoroborate, lithium perchlorate, lithium hexafluoroarsenate, lithium bis(fluorosulfonyl)imide, lithium bis(trifluoromethanesulfonyl)imide, lithium trifluoromethanesulfonate, lithium difluorophosphate, lithium difluorooxalatoborate, lithium dioxalatoborate, lithium difluorodioxalatophosphate, and lithium tetrafluorooxalatophosphate.

[0246] In some embodiments, the solvent can be selected from at least one of ethylene carbonate, propylene carbonate, ethyl methyl carbonate, diethyl carbonate, dimethyl carbonate, dipropyl carbonate, methyl propyl carbonate, ethyl propyl carbonate, butylene carbonate, fluoroethylene carbonate, methyl formate, methyl acetate, ethyl acetate, propyl acetate, methyl propionate, ethyl propionate, propyl propionate, methyl butyrate, ethyl butyrate, 1,4-butyrolactone, cyclopentane sulfone, dimethyl sulfone, methyl ethyl sulfone and diethyl sulfone.

[0247] In some embodiments, the electrolyte may further include additives, such as negative electrode film-forming additives, positive electrode film-forming additives, and additives that can improve certain battery properties, such as additives that improve battery overcharge performance, additives that improve battery high or low temperature performance, etc.

[0248] [Isolation film]

[0249] In some embodiments, the secondary battery further includes a separator. The present application has no particular limitation on the type of separator, and any known porous separator with good chemical stability and mechanical stability can be selected.

[0250] In some embodiments, the material of the isolation membrane can be selected from at least one of glass fiber, non-woven fabric, polyethylene, polypropylene and polyvinylidene fluoride. The isolation membrane can be a single-layer film or a multi-layer composite film, without particular limitation. When the isolation membrane is a multi-layer composite film, the materials of each layer can be the same or different, without particular limitation.

[0251] In some embodiments, the positive electrode sheet, the negative electrode sheet, and the separator may be formed into an electrode assembly by a winding process or a lamination process.

[0252] In some embodiments, the secondary battery may include an outer package, which may be used to encapsulate the electrode assembly and the electrolyte.

[0253] In some embodiments, the outer packaging of the secondary battery may be a hard shell, such as a hard plastic shell, an aluminum shell, a steel shell, etc. The outer packaging of the secondary battery may also be a soft package, such as a bag-type soft package. The material of the soft package may be plastic, and examples of the plastic include polypropylene, polybutylene terephthalate, and polybutylene succinate.

[0254] The present application has no particular limitation on the shape of the secondary battery, which may be cylindrical, square or any other shape. Figure 1 The secondary battery 5 is a square structure as an example.

[0255] In some embodiments, reference Figure 2 , the outer packaging may include a shell 51 and a cover plate 53. Among them, the shell 51 may include a bottom plate and a side plate connected to the bottom plate, and the bottom plate and the side plate enclose a receiving cavity. The shell 51 has an opening connected to the receiving cavity, and the cover plate 53 can be covered on the opening to close the receiving cavity. The positive electrode sheet, the negative electrode sheet and the isolation membrane can form an electrode assembly 52 through a winding process or a lamination process. The electrode assembly 52 is encapsulated in the receiving cavity. The electrolyte is infiltrated in the electrode assembly 52. ​​The number of electrode assemblies 52 contained in the secondary battery 5 can be one or more, and those skilled in the art can select according to specific actual needs.

[0256] In some embodiments, secondary batteries may be assembled into a battery module. The number of secondary batteries contained in the battery module may be one or more, and the specific number may be selected by those skilled in the art according to the application and capacity of the battery module.

[0257] Figure 3 4 is an example of a battery module. Figure 3 In the battery module 4, the plurality of secondary batteries 5 may be arranged in sequence along the length direction of the battery module 4. Of course, they may also be arranged in any other manner. Further, the plurality of secondary batteries 5 may be fixed by fasteners.

[0258] Optionally, the battery module 4 may further include a housing having a receiving space, and the plurality of secondary batteries 5 are received in the receiving space.

[0259] In some embodiments, the battery modules described above may also be assembled into a battery pack. The battery pack may contain one or more battery modules, and the specific number may be selected by those skilled in the art according to the application and capacity of the battery pack.

[0260] Figure 4 and Figure 5 1 is a battery pack 1 as an example. Figure 4 and Figure 5The battery pack 1 may include a battery box and a plurality of battery modules 4 disposed in the battery box. The battery box includes an upper box body 2 and a lower box body 3. The upper box body 2 can cover the lower box body 3 and form a closed space for accommodating the battery modules 4. The plurality of battery modules 4 can be arranged in the battery box in any manner.

[0261] In addition, the present application also provides an electrical device, which includes at least one of the secondary battery, battery module, or battery pack provided in the present application. The secondary battery, battery module, or battery pack can be used as a power source for the electrical device, and can also be used as an energy storage unit for the electrical device. The electrical device may include mobile devices (such as mobile phones, laptops, etc.), electric vehicles (such as pure electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles, electric bicycles, electric scooters, electric golf carts, electric trucks, etc.), electric trains, ships and satellites, energy storage systems, etc., but are not limited thereto.

[0262] As the electrical device, a secondary battery, a battery module or a battery pack may be selected according to its usage requirements.

[0263] Figure 6 The power consumption device is taken as an example. The power consumption device is a pure electric vehicle, a hybrid electric vehicle, or a plug-in hybrid electric vehicle. In order to meet the high power and high energy density requirements of the power consumption device for the secondary battery, a battery pack or a battery module can be used.

[0264] Another example of a device may be a mobile phone, a tablet computer, a notebook computer, etc. Such a device is usually required to be thin and light, and a secondary battery may be used as a power source.

[0265] Example

[0266] Hereinafter, the embodiments of the present application will be described. The embodiments described below are exemplary and are only used to explain the present application, and should not be construed as limiting the present application. If no specific techniques or conditions are indicated in the embodiments, the techniques or conditions described in the literature in this area or the product specifications are used. If the manufacturer is not indicated in the reagents or instruments used, they are all conventional products that can be obtained commercially.

[0267] Example 1

[0268] (1) Preparation of positive electrode slurry:

[0269] Preparation of the first lithium iron phosphate salt particles:

[0270] Weigh lithium carbonate, ferric oxide, phosphoric acid, glucose, titanium dioxide (based on the total weight of lithium iron phosphate particles, the amount of titanium dioxide added is such that the titanium content in the prepared lithium iron phosphate particles is 5000ppm) and polyaniline, wherein the weight ratios of Li element, Fe element and P element are such that Fe:P=0.968:1, Li:Fe=1:0.98, and the weight ratio of glucose to polyaniline is such that glucose:polyaniline=1:2. The amount of glucose added is such that after the first sintering is completed, the carbon content accounts for 0.15% of the weight of the lithium iron phosphate precursor. Add water to the above substances to obtain a mixture slurry.

[0271] Use a ball mill to mix the mixture slurry evenly, grind it with a sand mill to obtain a slurry with a solid content of 38% and a Dv50 of 0.40μm, and spray dry it (the negative pressure of the high-speed spray dryer is -650~-200Pa, the inlet temperature is 300℃~360℃, and the outlet temperature is 100℃~140℃). The dried reactants are loaded into a sintering furnace for the first sintering, and the heating rate is controlled at 5℃ / min, the insulation temperature is controlled at 650℃, and the insulation time is 4h. After the material is cooled, it is crushed by a mechanical mill to obtain a powder.

[0272] Glucose as a carbon source and polyaniline as a carbon film-forming agent are added to the obtained powder, and then mixed with water to obtain a material with a solid content of 40%. Among them, the amount of glucose and polyaniline added satisfies that the carbon content of the product after the second sintering is 1.2% (based on the total weight of the lithium iron phosphate salt particles), and the weight ratio of glucose to polyaniline satisfies glucose: polyaniline = 1:2. The slurry is obtained by ball milling and sand milling, and the Dv50 of the insoluble matter in the slurry is 550nm. Spray drying is performed (the negative pressure of the high-speed spray dryer is -650 to -200Pa, the inlet temperature is 300℃ to 360℃, and the outlet temperature is 100℃ to 140℃). The dried reactants are loaded into a sintering furnace for a second low-temperature sintering (the heating rate is controlled at 5℃ / min, the sintering temperature is 750℃, and the sintering time is 4h). After the material is cooled, it is crushed for the second time to an average particle size of 870 nm. After demagnetization, lithium iron phosphate salt particles are obtained, with a carbon content of 1.2% and a Ti content of 5000 ppm in the lithium iron phosphate salt particles.

[0273] The first lithium iron phosphate salt particles and lithium manganese iron phosphate salt particles (purchased from Guangdong Bangpu Recycling Technology Co., Ltd., item number CPP-001-001) are blended according to the area ratio listed in Table 1 to obtain a positive electrode active material, and the above-mentioned blended positive electrode active material, conductive agent conductive carbon black, binder polyvinylidene fluoride and dispersant PVP are mixed in a weight percentage of 93:4.0:2.5:0.5 and N-methylpyrrolidone is added, and the mixture is fully mixed, stirred, and dispersed to form a positive electrode slurry.

[0274] (2) Preparation of positive electrode sheet:

[0275] The viscosity of the mixed and stirred slurry is adjusted to 8000-20000mPa.s until the slurry is not stratified, and the slurry is coated with 420mg / 1540mm by double-sided double-control coating equipment. 2 It is coated on the surface of the Al foil substrate, and then dried, cold pressed, cut and sliced ​​to finally obtain the positive electrode sheet.

[0276] (3) Preparation of negative electrode sheet:

[0277] Artificial graphite, conductive carbon black, binder styrene-butadiene rubber (SBR) and thickener sodium carboxymethyl cellulose (CMC) were mixed evenly according to a weight percentage of 95:1.0:2.0:2.0, and deionized water was added. After stirring and dispersion, a negative electrode slurry was obtained. The negative electrode slurry was prepared at 211 mg / 1540 mm 2 It is coated on the Cu foil substrate, and then dried, cold pressed, cut and sliced ​​to obtain the negative electrode sheet;

[0278] (4) Preparation of batteries:

[0279] Stack the positive electrode sheet, isolation film, and negative electrode sheet in order. The isolation film must be able to isolate the anode and cathode. The bare battery cell is obtained by winding, and the bare battery cell is placed in an outer package. The electrolyte is injected, and after packaging, formation, exhaust and other processes, a lithium-ion battery is finally obtained.

[0280] Example 2

[0281] The difference between Example 2 and Example 1 is that the primary average particle size of the lithium manganese iron phosphate particles is 210 nm and the specific surface area is 12 m 2 / g, the carbon content is 1.4% by weight, and the lithium manganese iron phosphate salt particles are purchased from Guangdong Brunp Recycling Technology Co., Ltd. with the item number CPP-001-002.

[0282] Example 3

[0283] The difference between Example 3 and Example 2 is that the primary average particle size of the lithium manganese iron phosphate particles is 120 nm and the specific surface area is 15 m 2 / g, the carbon content is 1.65% by weight, and the lithium manganese iron phosphate salt particles are purchased from Guangdong Brunp Recycling Technology Co., Ltd. with the item number SH-LMFP-1.

[0284] Example 4

[0285] The difference between Example 4 and Example 2 is that the primary average particle size of the lithium manganese iron phosphate particles is 600 nm and the specific surface area is 10 m 2 / g, the lithium manganese iron phosphate salt particles were purchased from Guangdong Brunp Recycling Technology Co., Ltd. with the item number SH-LMFP-2.

[0286] Example 5

[0287] The difference between Example 5 and Example 2 is that the primary average particle size of the first lithium iron phosphate salt particles is 250 nm and the specific surface area is 9.5 m 2 / g.

[0288] Example 6

[0289] The difference between Example 6 and Example 2 is that the primary average particle size of the first lithium iron phosphate salt particles is 300 nm and the specific surface area is 7.5 m 2 / g.

[0290] Example 7

[0291] The difference between Example 7 and Example 2 is that the primary average particle size of the first lithium iron phosphate salt particles is 4000 nm and the specific surface area is 4.5 m 2 / g.

[0292] Example 8

[0293] The difference between Example 8 and Example 2 is that the primary average particle size of the lithium manganese iron phosphate particles is 480nm and the specific surface area is 11m 2 / g, the lithium iron manganese phosphate salt particles were purchased from Guangdong Brunp Recycling Technology Co., Ltd. with the item number CPP-001-003.

[0294] Example 9

[0295] The difference between Example 9 and Example 2 is that the primary average particle size of the first lithium iron phosphate salt particles is 3000 nm and the specific surface area is 5 m 2 / g.

[0296] Example 10

[0297] The difference between Example 10 and Example 2 is that the primary average particle size of the first lithium iron phosphate salt particles is 3500 nm and the specific surface area is 4.6 m 2 / g.

[0298] Embodiment 11

[0299] The difference between Example 11 and Example 2 is that the primary average particle size of the first lithium iron phosphate salt particles is 500 nm and the specific surface area is 7 m 2 / g.

[0300] Example 12

[0301] The difference between Example 12 and Example 2 is that the specific surface area of ​​the lithium manganese iron phosphate particles is 17m 2 / g, the carbon content is 1.8% by weight, and the lithium manganese iron phosphate salt particles are purchased from Guangdong Brunp Recycling Technology Co., Ltd. with the item number CPP-001-005.

[0302] Example 13

[0303] The difference between Example 13 and Example 2 is that the specific surface area of ​​the lithium manganese iron phosphate particles is 10m 2 / g, the carbon content is 1.2% by weight, and the lithium manganese iron phosphate salt particles are purchased from Guangdong Brunp Recycling Technology Co., Ltd. with the item number CPP-001-009.

[0304] Embodiment 14

[0305] The difference between Example 14 and Example 2 is that the specific surface area of ​​the first lithium iron phosphate salt particles is 5.5 m 2 / g, and the carbon content is 1.15% by weight.

[0306] Embodiment 15

[0307] The difference between Example 15 and Example 2 is that the specific surface area of ​​the first lithium iron phosphate salt particles is 5m 2 / g, and the carbon content is 1.2% by weight.

[0308] Example 16

[0309] The difference between Example 16 and Example 2 is that the titanium content of the first lithium iron phosphate salt particles is 2500 ppm.

[0310] Embodiment 17

[0311] The difference between Example 17 and Example 2 is that the titanium content of the first lithium iron phosphate salt particles is 6000 ppm.

[0312] Embodiment 18

[0313] The difference between Example 18 and Example 2 is that vanadium pentoxide is used instead of titanium dioxide, and the specific surface area of ​​the first lithium iron phosphate salt particles is 8m 2 / g.

[0314] Embodiment 19

[0315] The difference between Example 19 and Example 2 is that niobium pentoxide is used instead of titanium dioxide.

[0316] Embodiment 20

[0317] The difference between Example 20 and Example 2 is that the specific surface area of ​​the first lithium iron phosphate salt particles is 3m 2 / g, and the carbon content is 0.8% by weight.

[0318] Embodiment 21

[0319] The difference between Example 21 and Example 2 is that the specific surface area of ​​the first lithium iron phosphate salt particles is 12 m 2 / g, and the carbon content is 1.4% by weight.

[0320] Embodiment 22

[0321] The difference between Example 22 and Example 2 is that the primary average particle size of the lithium manganese iron phosphate particles is 500 nm and the specific surface area is 10.5 m 2 / g, the lithium iron manganese phosphate salt particles were purchased from Guangdong Brunp Recycling Technology Co., Ltd. with the item number CPP-001-013.

[0322] Embodiment 23

[0323] The difference between Example 23 and Example 2 is that the primary average particle size of the lithium manganese iron phosphate particles is 140 nm and the specific surface area is 20 m 2 / g, the lithium iron manganese phosphate salt particles were purchased from Guangdong Brunp Recycling Technology Co., Ltd. with the item number CPP-001-026.

[0324] Embodiment 24

[0325] The difference between Example 24 and Example 2 is that the area of ​​the manganese iron phosphate lithium salt particles accounts for 70%, and the area of ​​the first lithium iron phosphate salt particles accounts for 30%.

[0326] Embodiment 25

[0327] The difference between Example 25 and Example 2 is that the area ratio of the manganese iron phosphate lithium salt particles is 98%, and the area ratio of the first lithium iron phosphate salt particles is 2%.

[0328] Embodiment 26

[0329] The difference between Example 26 and Example 2 is that the titanium content of the first lithium iron phosphate salt particles is 1000 ppm.

[0330] Embodiment 27

[0331] The difference between Example 27 and Example 2 is that the titanium content of the first lithium iron phosphate salt particles is 10000 ppm.

[0332] Embodiment 28

[0333] (1) Preparation of positive electrode slurry:

[0334] The sources / preparation methods of the manganese iron phosphate lithium salt particles and the first lithium iron phosphate salt particles are exactly the same as those in Example 2.

[0335] The second lithium iron phosphate salt particles were purchased from Xiamen Tungsten New Energy Technology Co., Ltd. with the item number CPF-014-001.

[0336] The manganese iron phosphate lithium salt particles, the first lithium iron phosphate salt particles and the second lithium iron phosphate salt particles are blended according to the area ratio listed in Table 1 to obtain a positive electrode active material, the above-blended positive electrode active material, conductive agent conductive carbon black, binder polyvinylidene fluoride and dispersant PVP are mixed in a weight percentage of 93:4.0:2.5:0.5, and N-methylpyrrolidone is added, and the mixture is fully mixed, stirred, and dispersed to form a positive electrode slurry.

[0337] (2) Preparation of positive electrode sheet:

[0338] Exactly the same as Example 2.

[0339] (3) Preparation of negative electrode sheet:

[0340] Exactly the same as Example 2.

[0341] (4) Preparation of batteries:

[0342] Exactly the same as Example 2.

[0343] Embodiment 29

[0344] The difference between Example 29 and Example 28 is that the area of ​​the manganese iron phosphate lithium salt particles accounts for 70%, the area of ​​the first lithium iron phosphate salt particles accounts for 25%, and the area of ​​the second lithium iron phosphate salt particles accounts for 5%.

[0345] Embodiment 30

[0346] The difference between Example 30 and Example 28 is that the area of ​​the manganese iron phosphate lithium salt particles accounts for 65%, the area of ​​the first lithium iron phosphate salt particles accounts for 25%, and the area of ​​the second lithium iron phosphate salt particles accounts for 10%.

[0347] Embodiment 31

[0348] The difference between Example 31 and Example 28 is that the area of ​​the manganese iron phosphate lithium salt particles accounts for 74%, the area of ​​the first lithium iron phosphate salt particles accounts for 25%, and the area of ​​the second lithium iron phosphate salt particles accounts for 1%.

[0349] Embodiment 32

[0350] The difference between Example 32 and Example 28 is that the primary average particle size of the second lithium iron phosphate salt particles is 30 nm and the specific surface area is 14 m 2 / g, the second lithium iron phosphate salt particles were purchased from Xiamen Tungsten New Energy Technology Co., Ltd. with the item number XW-LFP-1.

[0351] Embodiment 33

[0352] The difference between Example 33 and Example 28 is that the primary average particle size of the second lithium iron phosphate salt particles is 200 nm and the specific surface area is 11 m 2 / g, the second lithium iron phosphate salt particles were purchased from Xiamen Tungsten New Energy Technology Co., Ltd. with the item number XW-LFP-2.

[0353] Embodiment 34

[0354] The difference between Example 34 and Example 28 is that the aspect ratio of the second lithium iron phosphate salt particles is 1.3, the ratio of the (020) crystal plane diffraction peak intensity to the (211) crystal plane diffraction peak intensity W = 1.03, and the second lithium iron phosphate salt particles were purchased from Xiamen Tungsten New Energy Technology Co., Ltd. with the item number XW-LFP-3.

[0355] Embodiment 35

[0356] The difference between Example 35 and Example 28 is that the aspect ratio of the second lithium iron phosphate salt particles is 1.3, the ratio of the (020) crystal plane diffraction peak intensity to the (211) crystal plane diffraction peak intensity of the second lithium iron phosphate salt particles is W = 1.08, and the second lithium iron phosphate salt particles were purchased from Xiamen Tungsten New Energy Technology Co., Ltd. with the item number XW-LFP-4.

[0357] Comparative Example 1

[0358] The difference between Comparative Example 1 and Example 2 is that the first lithium iron phosphate salt particles are not included.

[0359] Comparative Example 2

[0360] The difference between Comparative Example 2 and Example 28 is that the first lithium iron phosphate salt particles are not included.

[0361] 2. Battery performance test

[0362] 1) Primary average particle size

[0363] The first lithium iron phosphate particles:

[0364] The pole piece is cut open perpendicularly to the large surface of the pole piece by an argon ion beam to expose the cross section, which is photographed by a scanning electron microscope, and the longest diameter of the first lithium iron phosphate salt particles is statistically analyzed by the long diameter statistical method. Among them, "primary average particle size" refers to the average value of the primary particle size of all particles, which is numerically equal to the total particle size value divided by the total number of particles. Among them, the primary particle size in the cross-section diagram refers to the longest distance connected by two points through the edge. Specifically, the total number of first lithium iron phosphate salt particles with a primary particle size greater than 80nm and the primary particle size of the first lithium iron phosphate salt particles with a primary particle size greater than 80nm can be counted in the electron microscope scanning photo, and the primary average particle size of the first lithium iron phosphate salt particles = the primary particle size of the total first lithium iron phosphate salt particles / the total number of first lithium iron phosphate salt particles. Among them, in the above-mentioned particle size statistical process, particles with a primary average particle size less than or equal to 80nm are not included in the statistical range.

[0365] Second lithium iron phosphate particles:

[0366] The pole piece is cut open perpendicularly to the large surface of the pole piece by an argon ion beam to expose the cross section, which is photographed by a scanning electron microscope, and the longest diameter of the second lithium iron phosphate salt particles is statistically analyzed by the long diameter statistical method. Among them, "primary average particle size" refers to the average value of the primary particle size of all particles, which is numerically equal to the total particle size value divided by the total number of particles. Among them, the primary particle size in the cross-section diagram refers to the longest distance connected by two points on the edge. Specifically, the total number of second lithium iron phosphate salt particles with a primary particle size greater than 10nm and the primary particle size of the second lithium iron phosphate salt particles with a primary particle size greater than 10nm can be counted in the electron microscope scanning photo, and the primary average particle size of the second lithium iron phosphate salt particles = the primary particle size of the total second lithium iron phosphate salt particles / the total number of second lithium iron phosphate salt particles. Among them, in the above particle size statistical process, particles with a primary average particle size less than or equal to 10nm are not included in the statistical range.

[0367] Lithium manganese iron phosphate particles:

[0368] The pole piece is cut open perpendicularly to the large surface of the pole piece by an argon ion beam to expose the cross section, which is photographed by a scanning electron microscope, and the longest diameter of the lithium iron manganese phosphate salt particles is statistically analyzed by the long diameter statistical method. Among them, the "primary average particle size" refers to the average value of the primary particle size of all particles, which is numerically equal to the total particle size value divided by the total number of particles. Among them, the primary particle size in the cross-section diagram refers to the longest distance connected by two points through the edge. Specifically, the total number of lithium iron manganese phosphate salt particles with a primary particle size greater than 10nm and the primary particle size of lithium iron manganese phosphate salt particles with a primary particle size greater than 10nm can be counted in the electron microscope scanning photo, and the primary average particle size of lithium iron manganese phosphate salt particles = the primary particle size of the total lithium iron manganese phosphate salt particles / the total number of lithium iron manganese phosphate salt particles. Among them, in the above-mentioned particle size statistical process, particles with a primary average particle size less than or equal to 10nm are not included in the statistical range.

[0369] 2) Dv50

[0370] With reference to GB / T19077.1-2016, the Dv50 value of the particles was measured using a laser particle size analyzer (Malvern Master Size 3000). In addition, the Dv10, Dv90, and Dv99 of the present application were also measured in the same manner.

[0371] 3) Specific surface area

[0372] The specific surface area was tested by gas adsorption method according to the GB / T19587-2017 test standard, as follows: lithium iron phosphate salt particles / lithium manganese iron phosphate salt particles were taken as samples, the sample tube was immersed in -196°C liquid nitrogen, and the adsorption amount of nitrogen on the solid surface at different pressures was measured at a relative pressure of 0.05-0.30. The monolayer adsorption amount of the sample was obtained based on the BET multilayer adsorption theory and its formula, thereby calculating the specific surface area of ​​the material.

[0373] 4) Carbon content

[0374] The first lithium iron phosphate salt particles / the second lithium iron phosphate salt particles / the lithium iron manganese phosphate salt particles are burned in a high-frequency induction furnace and then the carbon content is tested by infrared absorption method. The specific testing process is based on the standard GB / T 20123-2006 / ISO15350:2000.

[0375] 5) Content of Q element (eg Ti element) in the first lithium iron phosphate salt particles

[0376] The content of Q element in the first lithium iron phosphate salt particles is tested with reference to GB / T 33822-2017.

[0377] 6) Area ratio

[0378] The areas of the lithium iron phosphate particles, the first lithium iron phosphate particles, and the second lithium iron phosphate particles were obtained by statistically analyzing the scanning electron microscope images of the obtained electrode sections using Avizo 3D software, and the corresponding area ratios were obtained by dividing the areas of the respective particles by the total area.

[0379] 7) The ratio of the diffraction peak intensity of the (020) crystal plane to the diffraction peak intensity of the (211) crystal plane W

[0380] The diffraction peak intensity ratio of the second lithium iron phosphate salt particles was tested by X-rays. The second lithium iron phosphate salt particles were placed on the test platform of the X-ray diffractometer (model: Shimadzu XRD-7000) using a copper target X-ray diffractometer. The starting angle of the scan was 10°, the ending angle was 90°, the step length was 0.013, and then the test was started to obtain the diffraction pattern of the second lithium iron phosphate salt particles in the diffraction angle range of 10° to 90°. The ratio W of the diffraction peak intensity of the (020) crystal plane to the diffraction peak intensity of the (211) crystal plane was determined based on the diffraction pattern.

[0381] 8) Aspect ratio

[0382] The aspect ratio is the ratio of the diameter of the major axis of a primary particle to the diameter of the minor axis. Assuming the diameter in the major axis is a and the diameter in the minor axis is b, the aspect ratio = a / b. This parameter is often used to describe the morphology of particles and can be used to measure their sphericity.

[0383] Test method: Take the cold pressed pole piece, cut it open perpendicular to the pole piece's large surface with an Ar particle beam, expose the end face, and obtain an image with a scanning electron microscope. Then analyze the scanning electron microscope image of the pole piece section with image software, measure the long diameter a and short diameter b of the particle, and obtain their ratio, which is the aspect ratio of the particle.

[0384] 9) The capacity ratio η of the first lithium iron phosphate particles in the embodiment and the comparative example when discharged to 3.2V and discharged to 2.0V respectively

[0385] First, prepare a button cell. The specific button cell preparation process is as follows: mix 2.0000g of the first lithium iron phosphate salt particles with 0.1111g of conductive carbon black and 0.1111g of polyvinylidene fluoride, and then add them to 2.5g of organic solvent N-methylpyrrolidone, and mix them thoroughly to form a slurry. The slurry is coated on aluminum foil with a coating thickness of 140 microns, vacuum dried at 120°C for 2h, and punched into a disc with a diameter of 13mm using a puncher. Use a tablet press to press the tablet at 10Mpa, and vacuum heat preservation at 120°C for 12h to obtain a positive electrode. Weigh the weight of the positive electrode, where the loading amount of the first lithium iron phosphate salt particles is 11-12mg. Button cells were assembled in an argon-protected glove box, with a metal lithium sheet as the negative electrode, an electrolyte of a 1:1 volume ratio of EC (ethylene carbonate) and DMC (1,2-dimethyl carbonate) mixed solvent, LiPF6 electrolyte, and a Celgard 2400 microporous polyethylene membrane as the separator.

[0386] The prepared button cell was tested for electrical performance on a blue electric tester. Specifically, the button cell was charged and discharged twice at a constant current of 0.1C within a voltage range of 2.0V to 3.75V, and then charged and discharged once at a constant current of 1C. In the charge and discharge test at a rate of 1C, the capacity value extracted when the discharge voltage was 3.2V was recorded as C1, and the capacity value extracted when discharged to 2.0V was recorded as C2, and η = C1 / C2. The charging process includes constant voltage charging, constant voltage of 3.75V, and constant voltage cut-off current of 50μA.

[0387] 10) Manganese dissolution

[0388] After 100 cycles, fully charge the cell and disassemble it in the glove box. After taking out the anode electrode in the drying room, use a ceramic knife to gently scrape 1g of material from the center of the electrode to ensure that the entire active material layer is scraped off to avoid different manganese content at different thicknesses. Seal it with a ziplock bag and send it to the laboratory. Prepare an electronic scale, heating plate, 150ml quartz beaker, watch glass, funnel, 100ml volumetric flask, pliers (heat-insulating gloves), weighing spoon, dust-free paper, etc.; confirm whether the calibration date of the electronic scale is within the validity period. It cannot be used after the validity period has expired and needs to be recalibrated; turn on the power, and the heating plate can heat up to 250℃ normally; weigh 0.2000±0.005g of powder in a beaker; acidification treatment: the configuration volume ratio is 1:4

[0389] (concentrated sulfuric acid: ultrapure water = 1:4) dilute sulfuric acid solution; add 20ml of the prepared dilute sulfuric acid solution to the beaker; turn on the heating plate for preheating in advance, and place the sample for digestion for 30 minutes after the temperature reaches 250℃, and place a quartz cover on the mouth of the beaker to reduce the volatilization of the acid; after the sample is digested for 30in, take it out and cool it to room temperature; transfer the digested sample to a 100ml glass volumetric flask to make up the volume; then proceed according to the ICP standard test process: the test equipment temperature is 22+2℃, and the humidity is <60%; the test method selects the trace element method; run the calibration standard: use the configured standard solution to determine the standard curve; select the element as Mn; finally, the Mn dissolution amount can be obtained after testing.

[0390] 11) Solid content of positive electrode slurry

[0391] Prepare an electronic balance (accuracy 0.0001), an oven, and a glass drying tray. Take 8-10g of the positive electrode slurry sample and spread it evenly on the sample tray, and record the mass of the slurry before drying as A. Cover the oven door and heat it. As the heating progresses, the temperature in the furnace continues to rise, rising to 130°C for 5 hours. After drying, cool it in the oven and take it out, record the mass of the slurry after drying, perform multiple drying, and record the mass after drying as B after the sample mass is constant. Slurry solid content = (A / B) × 100%.

[0392] 12) Pole compaction density

[0393] The "pole piece compaction density" referred to in this application refers to the "ultimate compaction density" of the pole piece, and the test method is as follows:

[0394] The double-sided coated electrode is cold pressed by a roller press to test the elongation of the electrode after cold pressing and to evaluate the flexibility of the electrode after cold pressing.

[0395] By increasing the pressure of the roller press, pole pieces with different compaction densities will be obtained. As the pressure increases, the compaction density of the pole piece increases, the elongation of the pole piece increases, and the flexibility of the pole piece decreases. Too high an elongation of the pole piece can easily cause the pole piece to warp, and too low a flexibility of the pole piece can easily cause the pole piece to break brittlely. Therefore, the smaller of the compaction density corresponding to the elongation of the pole piece of 6‰ or the number of times the pole piece's flexibility is folded 3 times is defined as the limit compaction density.

[0396] The compacted density is calculated by dividing the weight of the single-sided positive electrode film layer by the volume of the positive electrode film layer.

[0397] 13) Gram capacity

[0398] The specific test process is briefly described as follows: (1) Place the battery in a 40°C oven environment and let it stand for 2 hours until the battery temperature remains at 40°C; (2) Discharge the battery at a constant current of 1 / 3C to 2.0V; (3) Pause for 5 minutes; (4) Charge the battery at a constant current of 1 / 3C to 4.1V, and then charge at a constant voltage of 4.1V until the cut-off current is 0.05C; (5) Pause for 5 minutes; (6) Discharge the battery at a constant current of 1 / 3C to 2.0V. This step is the actual battery cell test capacity. Combined with the mass of the positive electrode active material, the gram capacity of the battery can be calculated. Gram capacity = capacity / mass of the positive electrode active material.

[0399] 14) High temperature storage performance

[0400] The high temperature storage performance was characterized by storing the battery at 60°C in a fully charged state (charged to 4.1V) and detecting the time it takes for the battery capacity to decay to 80% of the initial value.

[0401] 1. Leave it for 10 minutes, and discharge it at a constant current of 0.33Cn (Cn is the capacity of the battery at 40°C and 1 / 3C) to 2V.

[0402] 2. Leave it for 10 minutes, charge at a constant current of 0.33Cn to 4.1V, then charge at a constant voltage with a cut-off current of 0.02Cn.

[0403] 3. Set aside for 2 hours, store at 60°C for 30 days, then take out and test the reversible capacity of the battery cell.

[0404] The specific test process is briefly described as follows: (1) Place the battery in a 40℃ oven environment and leave it for 2 hours until the battery temperature remains at 40℃; (2) Discharge at 1 / 3C constant current to 2.0V; (3) Pause for 5 minutes; (4) Charge at 1 / 3C constant current to 4.1V, then charge at 4.1V constant voltage to a cutoff current of 0.05C; (5) Pause for 5 minutes; (6) Discharge at 1 / 3C constant current to 2.0V. This step is the actual cell capacity test.

[0405] 4. Test regularly until the reversible capacity of the cell decays to 80% of the initial capacity.

[0406] 15) High temperature cycle performance

[0407] The high temperature cycle performance is characterized by adopting 1C / 1C cycle at 60°C and detecting the number of cycles when the battery capacity decays to 80% of the initial value.

[0408] The specific process is briefly described as follows: (1) Place the battery in a 45°C oven and leave it for 2 hours until the battery temperature remains at 25°C; (2) Charge at a constant current of 1C to 3.65V, and continue charging at a constant voltage until the charging current is less than 0.05C; (3) Pause for 5 minutes; (4) Discharge at a constant current of 1C to 2.5V; (5) Pause for 5 minutes. Steps (2) to (6) are one charge and discharge cycle of the battery. Repeat steps (2) to (6) until the battery capacity decays to 80% of the initial value.

[0409] III. Analysis of test results of various embodiments and comparative examples

[0410] The batteries of the embodiments and comparative examples were prepared according to the above methods, and various performance parameters were measured. The parameters of the positive electrode active material are shown in Table 1, and the performance test results are shown in Table 2.

[0411]

[0412]

[0413] Table 2: Performance test results

[0414]

[0415] According to the above results, the secondary batteries in Examples 1-31 all include a positive electrode sheet, a negative electrode sheet, a separator and an electrolyte, the positive electrode sheet includes a positive electrode active material, the positive electrode active material includes manganese iron phosphate lithium salt particles, and the primary average particle size of manganese iron phosphate lithium salt particles is 120-600nm, wherein the manganese dissolution amount of the secondary battery is ≤50ppm. From the comparison of Examples 1-31 and Comparative Examples 1-2, it can be seen that the secondary batteries of the embodiments of the present application have good high temperature storage performance. In addition, the secondary batteries of the embodiments of the present application also have good high temperature cycle performance and a higher solid content of the positive electrode slurry.

[0416] From the comparison between Examples 2, 9, and 11 and Examples 5-6, it can be seen that when the positive electrode active material also includes first lithium iron phosphate salt particles, and the primary average particle size s1 of the first lithium iron phosphate salt particles satisfies 500nm≤s1≤3000nm, the secondary battery of the embodiment of the present application has a lower manganese dissolution amount, better high temperature storage performance, better high temperature cycle performance, and a higher positive electrode slurry solid content.

[0417] From the comparison between Examples 2, 9, 10-11 and Examples 5-6, it can be seen that when the positive electrode active material also includes first lithium iron phosphate salt particles, and the primary average particle size s1 of the first lithium iron phosphate salt particles satisfies 500nm≤s1≤3500nm, the secondary battery of the embodiment of the present application has a lower manganese dissolution amount, better high temperature storage performance, better high temperature cycle performance, and a higher positive electrode slurry solid content.

[0418] From the comparison between Examples 2, 7, 9, 10-11 and Examples 5-6, it can be seen that when the positive electrode active material also includes first lithium iron phosphate salt particles, and the primary average particle size s1 of the first lithium iron phosphate salt particles satisfies 500nm≤s1≤4000nm, the secondary battery of the embodiment of the present application has a lower manganese dissolution amount, better high temperature storage performance, and a higher positive electrode slurry solid content.

[0419] From the comparison between Example 2 and Examples 28-35, it can be seen that when the positive electrode active material also includes second lithium iron phosphate salt particles, and the primary average particle size s2 of the second lithium iron phosphate salt particles satisfies 30nm≤s2≤200nm, the secondary battery of the embodiment of the present application has a lower manganese dissolution amount, better high temperature storage performance, and better high temperature cycle performance.

[0420] From the comparison between Examples 2, 16-17 and Examples 26-27, it can be seen that, based on the total weight of the first lithium iron phosphate salt particles, when the Ti content in the first lithium iron phosphate salt particles is 2500-6000ppm, the secondary battery of the embodiment of the present application has better high temperature storage performance and higher gram capacity.

[0421] From the comparison between Examples 2, 14-15, 18, 20 and Example 21, it can be seen that when the specific surface area of ​​the first lithium iron phosphate salt particles is 3m 2 / g-8m 2 / g, the secondary battery of the embodiment of the present application has a lower manganese dissolution amount, a higher positive electrode slurry solid content, and a higher positive electrode sheet compaction density.

[0422] From the comparison between Examples 2, 10-11, 16 and Example 17, it can be seen that when the specific surface area of ​​the first lithium iron phosphate salt particles is 3m 2 / g-6m 2 / g, the secondary battery of the embodiment of the present application has good high-temperature storage performance, good high-temperature cycle performance, and high positive electrode sheet compaction density.

[0423] From the comparison between Examples 2, 14-15, and 20 and Example 21, it can be seen that, based on the total weight of the first lithium iron phosphate salt particles, the carbon content of the first lithium iron phosphate salt particles is Cx1 weight %, and when 0.8≤Cx1≤1.2, the secondary battery of the embodiment of the present application has better high-temperature storage performance, lower manganese dissolution, higher positive electrode slurry solid content, better high-temperature cycle performance, and higher positive electrode sheet compaction density.

[0424] From the comparison between Examples 2, 14-15, 20 and Example 21, it can be seen that when the ratio z1 of the specific surface area of ​​the first lithium iron phosphate salt particles to Cx1 satisfies 3.8≤z1≤5, the secondary battery of the embodiment of the present application has better high-temperature storage performance, lower manganese dissolution, higher positive electrode slurry solid content, better high-temperature cycle performance, and higher positive electrode sheet compaction density.

[0425] From the comparison between Examples 34-35 and Example 28, it can be seen that when the aspect ratio of the second lithium iron phosphate salt particles is ≥1.3, the secondary battery of the embodiment of the present application has better high-temperature storage performance, lower manganese dissolution, better high-temperature cycle performance, and higher gram capacity.

[0426] From the comparison between Examples 34-35 and Example 28, it can be seen that when the ratio W of the (020) crystal plane diffraction peak intensity to the (211) crystal plane diffraction peak intensity of the second lithium iron phosphate salt particles is ≥1.03, the secondary battery of the embodiment of the present application has better high-temperature storage performance, lower manganese dissolution, better high-temperature cycle performance, and higher gram capacity.

[0427] From the comparison between Examples 2, 12-13 and Example 23, it can be seen that when the specific surface area of ​​the lithium manganese iron phosphate particles is 10m 2 / g-17m 2 / g, the secondary battery of the embodiment of the present application has better high-temperature storage performance, lower manganese dissolution, better high-temperature cycle performance, and higher positive electrode sheet compaction density.

[0428] It should be noted that the present application is not limited to the above-mentioned embodiments. The above-mentioned embodiments are only examples, and the embodiments having the same structure as the technical idea and exerting the same effect within the scope of the technical solution of the present application are all included in the technical scope of the present application. In addition, without departing from the scope of the main purpose of the present application, various modifications that can be thought of by those skilled in the art to the embodiments and other methods of combining some of the constituent elements in the embodiments are also included in the scope of the present application.

Claims

1. A secondary battery, comprising a positive electrode sheet, a negative electrode sheet, a separator and an electrolyte, wherein the positive electrode sheet comprises a positive electrode active material, the positive electrode active material comprises lithium iron manganese phosphate salt particles, the primary average particle size of the lithium iron manganese phosphate salt particles is 120-600nm, wherein the manganese dissolution amount of the secondary battery is ≤50ppm. 2 . The secondary battery according to claim 1 , wherein the positive electrode active material further comprises first lithium iron phosphate salt particles, and a primary average particle size s1 of the first lithium iron phosphate salt particles satisfies 500 nm≤s1≤3000 nm.

3. The secondary battery according to claim 1 or 2, wherein based on the total area of ​​the positive electrode active material in the cross section of the positive electrode sheet, the area of ​​the first lithium iron phosphate salt particles accounts for 2%-30%, and the area of ​​the lithium manganese iron phosphate salt particles accounts for 70%-98%. 4 . The secondary battery according to claim 2 , wherein the positive electrode active material further comprises second lithium iron phosphate salt particles, and the primary average particle size s2 of the second lithium iron phosphate salt particles satisfies 30 nm≤s2≤200 nm.

5. The secondary battery according to claim 4, wherein based on the total area of ​​the positive electrode active material in the cross section of the positive electrode plate, the area of ​​the second lithium iron phosphate salt particles accounts for 1-10%; the area of ​​the first lithium iron phosphate salt particles accounts for 2-25%; the area of ​​the manganese iron phosphate lithium salt particles accounts for 70%-97%.

6. The secondary battery according to any one of claims 1 to 5, wherein the manganese iron phosphate lithium salt particles have a molecular formula Li m Fe x Mn r P y O j Q q , wherein Q comprises at least one of Al, Na, K, Mg, Cu, Cr, Zn, Pb, Ca, Co, Ni, Sr, Nb, V, Ti, B, S, Si, N, F, Cl, Br, 0.95≤m≤1.15, x>0, r>0, 0.9≤x+r≤1, 0.95≤y≤1, 3.5≤j≤4, 0≤q≤0.1, and / or The first lithium iron phosphate salt particles have a molecular formula of Li m1 Fe x1 P y1 O j1 Q1 q1 , wherein Q1 includes at least one of Al, Na, K, Mg, Cu, Mn, Cr, Zn, Pb, Ca, Co, Ni, Sr, Nb, V, Ti, B, S, Si, N, F, Cl, Br, 0.95≤m1≤1.15, 0.9≤x1≤1, 0.95≤y1≤1, 3.5≤j1≤4, 0<q1≤0.1, and / or The second lithium iron phosphate salt particles have a molecular formula of Li m2 Fe x2 P y2 O j2 Q2 q2 , wherein Q2 includes at least one of Al, Na, K, Mg, Cu, Mn, Cr, Zn, Pb, Ca, Co, Ni, Sr, Nb, V, Ti, B, S, Si, N, F, Cl, and Br, 0.95≤m2≤1.15, 0.9≤x2≤1, 0.95≤y2≤1, 3.5≤j2≤4, and 0≤q2≤0.

1.

7. The secondary battery according to claim 6, wherein in the first lithium iron phosphate salt particles, the Q1 includes at least one of Ti, V, Mg, and Nb, and the content of Ti, V, Mg and / or Nb is 1000-10000 ppm based on the total weight of the first lithium iron phosphate salt particles.

8. The secondary battery according to any one of claims 2 to 7, wherein the specific surface area of ​​the first lithium iron phosphate salt particles is 3 m 2 / g-8m 2 / g.

9. The secondary battery according to any one of claims 2 to 8, wherein the carbon content of the first lithium iron phosphate salt particles is Cx1% by weight, based on the total weight of the first lithium iron phosphate salt particles. 0.8≤Cx1≤2.

0.

10. The secondary battery according to any one of claims 1 to 9, wherein the primary average particle size of the lithium iron phosphate particles is 150-210 nm, the primary average particle size s1 of the first lithium iron phosphate particles satisfies 870 nm ≤ s1 ≤ 3000 nm, and / or the primary average particle size s2 of the second lithium iron phosphate particles satisfies 60 nm ≤ s2 ≤ 200 nm.

11. The secondary battery according to any one of claims 2 to 10, wherein the capacity ratio of the first lithium iron phosphate salt particles is η≥88%, and η is defined as: The battery using the first lithium iron phosphate salt particles as the positive electrode active material is charged and discharged twice at a constant current rate of 0.1C in the voltage range of 2.0V to 3.75V, and then charged and discharged once at a constant current rate of 1C. In the charge and discharge test at the rate of 1C, the capacity value extracted at a discharge voltage of 3.2V is recorded as C1, and the capacity value extracted and discharged to 2.0V is C2, and η=C1 / C2, wherein, The charging process includes constant voltage charging, constant voltage 3.75V, and constant voltage cut-off current 50μA.

12. The secondary battery according to any one of claims 2 to 11, wherein the first lithium iron phosphate salt particles satisfy at least one of (a) to (f): (a) Dv10 of the first lithium iron phosphate salt particles is ≥ 0.2 μm; (b) the Dv50 of the first lithium iron phosphate particles is 0.5-5 μm; (c) Dv90 of the first lithium iron phosphate salt particles is ≤10 μm; (d) Dv99 of the first lithium iron phosphate salt particles is ≤12 μm; (e) The powder compaction density of the first lithium iron phosphate salt under a pressure of 3 tons is ≥ 2.25 g / cm 3 ; (f) The powder resistivity of the first lithium iron phosphate salt is less than 60Ω·cm. 13 . The secondary battery according to claim 1 , wherein the aspect ratio of the second lithium iron phosphate salt particles is ≥1.

3. 14 . The secondary battery according to claim 1 , wherein the ratio W of the diffraction peak intensity of the (020) crystal plane to the diffraction peak intensity of the (211) crystal plane of the second lithium iron phosphate salt particles is ≥1.

03.

15. The secondary battery according to any one of claims 2 to 14, wherein the first lithium iron phosphate salt particles are mainly obtained by the following preparation method: Providing raw materials containing at least a lithium source, an iron source, a phosphorus source, a carbon film-forming agent, a carbon source, and a modifier, and performing at least two sintering steps, wherein: The temperature of the first sintering is 500℃-760℃; The temperature of the second sintering is 700℃-800℃.

16. The secondary battery according to claim 15, wherein the first lithium iron phosphate salt particles are mainly obtained by the following preparation method: Providing raw materials containing at least a lithium source, an iron source, a phosphorus source, a carbon source, a carbon film-forming agent, and a modifier, and performing at least two sintering steps, wherein: The carbon content of the material after the first sintering is 0.01 wt%-0.79 wt%; The carbon content of the material after the second sintering is 0.8 wt%-2.0 wt%.

17. The secondary battery according to claim 15 or 16, wherein the method for preparing the first lithium iron phosphate salt particles comprises the following steps: The first pulverization is performed after the first sintering, and the second pulverization is performed after the second sintering, wherein: The Dv50 of the product after the first crushing is 300nm-1200nm; The Dv50 of the product after the second pulverization is 500nm-5000nm.

18. An electrical device comprising the secondary battery according to any one of claims 1 to 17.

Citation Information

Patent Citations

  • Composite material and preparation method thereof

    CN111613786A

  • Lithium iron phosphate positive electrode active material, preparation method thereof, positive electrode plate and battery

    CN114068919A

  • Multi-position co-doped lithium manganese iron phosphate composite material, preparation method and secondary battery

    CN115863623A

  • Iron and phosphorus co-doped lithium manganese iron phosphate composite material, preparation method and secondary battery

    CN115995534A

  • Secondary battery, and battery module, battery pack and power device including same

    CN116830337A